Advancing subsurface characterization through borehole optical imaging: A comprehensive review - Ding-Jian Wang; Yunfeng Ge; Tao Wen; Zhiqiang Fan; Yahui Zhang (Tunnelling and Underground Space Technology, 2026)

Spatially explicit assessment of phosphorus runoff loss in Chinese paddy fields: An interpretable machine learning model - Junjia Qi; Yi Wang; Ying Zhao; Jian Liu; Yuchen Lv; Tida Ge; Zhenghui Lv; Haolin Yang; Pengfei Fan; Ziqi Mai (Soil and Tillage Research, 2026)

Explainable machine learning and Pareto optimization enable data-driven design of COF-TFN nanofiltration membranes for desalination - Shengnan Hao; Yulin Ge; Zhu Fan; Xiaoman Zhang; Zhanlin Ji; Dalei Song; Yingchao Dong (Desalination, 2026)

Wastewater nutrients valorization into biostimulant via engineered polyphosphate-accumulating bacterium - Xiaotong Ge; Xue Li; Zihao Fan; Xin Wang; Mengmeng Wang; Jingyun Yin; Xiaohua Song; Liyu Pan; Yuhu Zheng; Liuyan Yang (Bioresource Technology, 2026)

Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

Long-term particulate matter exposure and coronary inflammation: A large-scale cohort study assessed by pericoronary fat attenuation index - Yuan Xu; Yi Zhang; Ge Guo; Xin Meng; Jing Wei; Yuanyuan Fan; Jiageng Cai; Cencen Wu; Zhulan Cai; Penghui Zhao; Yuwen Ruan; Zhaowei Yin; et al. (Environmental Pollution, 2026)

Rapid preliminary screening of amine absorbents for post-combustion CO2 capture - Xi Tang; Bin Xu; Xiaoyi Gao; Xiaoshan Li; Ge Gao; Wen Chen; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2026)

Enterococcus in herbal fermentation: a genus-specific perspective on enzymatic capability, biotransformation outcomes and safety - Jiafei Tang; Shuo Zhang; Gui Xu; Mengxiao Cui; Xiutong Ge; Hui Gao; Fan Zhang (Archives of Microbiology, 2026)

Fine-scale mapping of urban evergreen and deciduous forests with high-resolution JL-1 multispectral satellite images using a weakly supervised deep neural network model - Yuan Zhang; Chentian Ge; Wenjia Yan; Guilian Zhang; Zhekui Fan; Chao Zhang (Urban Forestry & Urban Greening, 2026)

Spatial patterns of modern pollen deposition as a basis for paleoecological interpretation in deep lakes: Insights from Fuxian Lake, Southwest China - Fan Xu; Sidan Cui; Jinhao Dong; Yawen Ge; Wenlei Luo; Lixin Xu; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Stable and strengthened phosphorus removal across different influent phosphorus concentrations was achieved in a micro-pressure swirl reactor under long SRT through the synergy of PAO enrichment and glycogen-dominant carbon metabolism - Yuying Fan; Chen Dai; Xinyu Zhu; Qi Liu; Tong Zhang; Ge Yu; Wenai Liu; Dejun Bian (Journal of Environmental Chemical Engineering, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Adaptive seasonal management after eradicating invasive Spartina: A nature-based approach - Dong-Fan Xu; Qi Yuan; Hai-Qiang Guo; Bing Tan; Fei Quan; Zhe-Xiu Yu; Dong-Yang Han; Yu-Jiao Lu; Ying-Ying Hao; Si-Qi Zhou; Guang Ge; Bin Zhao; et al. (Ecological Engineering, 2026)

An antibacterial polypeptosome spray with virulence factors inhibition and antioxidant effects to heal antibiotic-resistant bacteria-infected diabetic wound - Caihong Chen; Mengjie Wu; Runxin Teng; Tao Wang; Biao Yang; Zhenghong Ge; Chang Li; Jianzhong Du; Zhen Fan (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

A multi-stage ROM-enhanced CFD-ML framework for efficient 3D urban wind-field prediction - Haiwei Chen; Jian Ge; Yifan Fan (Sustainable Cities and Society, 2026)

Pyrite geochemistry and sulfur isotopes track fluid evolution and Mo enrichment in the giant Jinduicheng porphyry deposit, central China - Xiaoyu Ge; Fan Yang; Martiya Sadeghi; Cun Zhang; Feifan Xu; Weidong Ren (Lithos, 2026)

Biotite unravels F-driven Mo mineralization and magmatic-hydrothermal evolution in the Chaijiagou porphyry deposit, North China - Fan Yang; Xiaoyu Ge; Zhenyu Qin; Lifeng Xu; Luyang Wang; Likun Yang; Hui Su (Journal of Geochemical Exploration, 2026)

Permeability evolution of coal fracture during injection-induced shear slip - Zhe Zhou; Fan Wang; Zhaolong Ge; Yuanting Zhang (Geomechanics for Energy and the Environment, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Multi-stage energy absorption of 3D hollow auxetic metamaterials at extremely low relative density - Dong Han; Zhongli Ge; Pengfei Li; Puhao Li; Peng Wang; Fan Yang (Engineering Structures, 2026)

ER stress promoted MAMs formation and ER-Mito Ca2+ transfer: implication for fluoride-induced hippocampal neuronal injury and cognitive deficits in mice - Siman Lin; LuYang Cao; Yuzhe Zhou; Shengdan Liu; Yue Yan; Qiwei Zhang; Quan Yuan; Yufei Gao; Ge Du; Jun Hu; Dongmei Wang; Hua Fan (Chemico-Biological Interactions, 2026)

Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands - Dongxue Fu; Huiwen Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

Study on the sustainability, resilience and co-governance of rural biomass energy systems: Based on an integrated perspective of ecology-community-culture-technology - Guorui Fan; Junxue Zhang; Zheheng Chen; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men (Biomass and Bioenergy, 2026)

Expression and Functional Characterisation of EhSWP 26 in Ecytonucleospora hepatopenaei : Insights From RNA Interference and Subcellular Localisation Analyses - Huiwen Jiang; Xiaohui Cao; Yi Qiao; Tingyue Liu; Jie Cheng; Ge Jiang; Xianping Fan; Haibo Wang; Kuipeng Fu; Hui Shen (Journal of Fish Diseases, 2026)
Ecytonucleospora hepatopenaei (EHP) is an obligate intracellular microsporidian that causes severe growth retardation in Penaeus vannamei (P. vannamei ), yet its pathogenic mechanisms remain incompletely clear. As the spore wall is essential for resisting environmental stress and mediating host invasion, characterising its protein components is critical for elucidating EHP biology. In this study, we identified and cloned a novel spore wall protein, EhSWP26. Sequence analysis revealed that EhSWP26 contains a 687 bp open reading frame encoding a 228‐amino‐acid polypeptide, lacking a signal peptide and transmembrane domain but harbouring a conserved MICSWaP (Microsporidia Spore Wall and Associated Proteins) domain characteristic of the microsporidian MICSWaPs family. Immunoelectron microscopy and indirect immunofluorescence assays demonstrated that EhSWP26 localises to the mature spore wall, where it is distributed in both the exospore and endospore layers. RNA interference further confirmed that silencing EhSWP26 significantly reduced its transcript level and led to a marked decrease in EHP spore load in shrimp hepatopancreas. Collectively, these findings indicate that EhSWP26 is a key structural and functional component associated with spore wall formation and host infection, likely playing an essential role in the EHP life cycle. This study enhances our understanding of EHP spore wall composition and function, provides a foundation for investigating its proliferation and infection mechanisms, and highlights EhSWP26 as a promising target for diagnostic development and therapeutic intervention in EHP disease of P. vannamei .

A Wind Data Quality Control Algorithm Utilizing Deep Learning-Based Association Test Rules - Ruidi Ma; Song Gao; Fan Jiang; Bo Yu; Haoqiang Tian; Yanchen Song; Yong Ge; Dianjun Ren; Chenxu Wang (Journal of Marine Science and Engineering, 2026)
Harnessing the powerful learning and modeling capabilities of artificial intelligence, this study introduces a deep learning-driven wind data quality control algorithm that employs correlation verification rules. By constructing a Dual-Track Information Fusion Network (DTF-Net), it captures local temporal variations in wind speed via the temporal track and uncovers physical coupling relationships among temperature, pressure, wind direction, and other variables through the global track. Integrating dynamic three-standard-deviation spike detection with 3δ-RMSE spatial validation based on deep learning predictions, the algorithm enables multi-dimensional collaborative anomaly detection in the absence of neighboring stations. Experimental findings demonstrate that the proposed method achieves Mean Absolute Errors (MAE) of 0.217, 0.398, and 0.462 for 1 h, 12 h, and 24 h wind speed forecasts, respectively, representing a 3.8–61.3% reduction compared to general-purpose models like AutoFormer, ITransformer, and FiLM. The anomaly detection rate for quality control ranges from 0.33% to 9.20%, effectively identifying data aberrations during buoy maintenance, equipment failures, and abrupt changes in short-term weather patterns. This study leverages the powerful learning and modeling capabilities of artificial intelligence to establish a novel and easily understandable intelligent quality-control paradigm for sparse ocean observation networks, providing direct practical value for improving the quality of marine meteorological data assimilation.

Retraction notice to “High-efficiency and low-carbon inactivation of UV resistant bacteria in reclaimed water by flow-through electrode system (FES)” [Sci. Total Environ. 904 (2023) 166297] - Yi-Ge Sun; Hao-Bin Wang; Yin-Hu Wu; Ke-Fan Cao; Zhuo Chen; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Science of The Total Environment, 2026)

Evaluation of microplastic removal performance and technologies in secondary effluent from typical sewage treatment processes using a self-developed enrichment–purification–separation-integrated device - Wenjuan Zhang; Xin Zhang; Li Fan; Siyu Wang; Shuang Ge; Rui Miao; Lei Wang; Yongtao Lv (Process Safety and Environmental Protection, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

Coupled Cl–F complexation and redox-halogen controls on Cu–Mo porphyry mineralization in the Mujicun deposit, North China - Fan Yang; Jingwen Mao; Xiaoyu Ge; Fuquan Yang; Zhenyu Qin; Likun Yang; Zhimin Wang (Journal of Geochemical Exploration, 2026)

KLF4/FOXF1 axis alleviates silicosis fibrosis by modulating fibroblast behavior and extracellular matrix remodeling - Xuesong Zhang; Hui Fan; Ge Qin; Bowen Fu; Botao Hu; Jingwen Fan; Youliang Zhao; Yuanmeng Qi; Xueyang Zhang; Wu Yao; Changfu Hao (Journal of Environmental Sciences, 2026)

High-efficiency solar evaporator based on tungsten oxide-doped carbon-modified cotton fabric for water-power co-generation - Chunyan Huang; Liqiang Yu; Fan Liu; Mingzhi Li; Zhili Li; Yuanyuan Ge (Chemical Engineering Journal, 2026)

Corrigendum to “Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands” [Biores. Technol. 455 (2026) 134788] - Dongxue Fu; Wenhui Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

Combined toxicity and mechanism of cadmium and neonicotinoid insecticide to rice (Oryza sativa L.): reduced antioxidant defence mediated by flavonoid - Zhaoxia Fan; Na Liu; Fei Ge; Feng Li; Wenjun Zhou; Juan Gao (ENGINEERING Environment, 2026)

Intensive management shifts litter decomposition from mycorrhizal to root-dominated pathway in a subtropical bamboo plantation - Wenhao Jin; Jiahe Wang; Jiangfei Ge; Xingcong Ma; Qifeng Wu; Shuai Shao; Chenfei Liang; Liyuan Peng; Xiaomin Ma; Yuchuan Fan; Yongfu Li; Junhui Chen; et al. (Applied Soil Ecology, 2026)

Research progress in kojibiose: structural insights, enzymatic synthesis, and applications in food and pharmaceutical industries - Zixuan Zhou; Hongyu Zhang; Tingting Lou; Suying Wang; Yicong Fan; Sisi Niu; Lifeng Ge (Critical Reviews in Food Science and Nutrition, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Investigation on the explosion characteristics and mechanisms of methane blended with hydrogen/ammonia - Tao Wang; Qiqi Liu; Zhenyi Liu; Changqi Liu; Mingzhi Li; Ran Sun; Shiqi Ge; Tao Fan; Zihao Xiu (Process Safety and Environmental Protection, 2026)

Emitter flow rate of drip irrigation regulates the distribution and bioaccumulation of typical PPCPs in reclaimed wastewater-irrigated soil-plant systems - Jing Jin; Songjing Li; Erping Cui; Chao Hu; Shengshu Li; Zhenchao Zhou; Bingjian Cui; Chuncheng Liu; Junying Chen; Ge Gao; Xiangyang Fan (Journal of Environmental Sciences, 2026)

Rayleigh seismic wave control by seismic metabarrier with low frequency band gaps: From lab-scale experiments to its engineering applications - Pengfei Huang; Zhiyi Chen; Hanbin Ge; Yifan Fan (Engineering Structures, 2026)

Structure and hepatoprotective activity of autophagy-related Butyriboletus roseoflavus polysaccharide - Zhen Sun; Huan Zhang; Dilida Yeerkenbieke; Lu Wang; Yongfeng Zhang; Chunyue Wang; Fan'ge Kong; Yu Li; Di Wang; Lanzhou Li (Carbohydrate Polymers, 2026)

Reconstructing 150 years of land-use history in an alpine-deep lake: A high-resolution multi-proxy sediment record from Fuxian Lake, China - Fan Xu; Sidan Cui; Jinhao Dong; Sihan Li; Yawen Ge; Wenlei Luo; Yuecong Li (CATENA, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

A Portable Smartphone-assisted Sensor for Detection of Iodate Based on Triphenylamine Oligomer - Yue Zhang; Mingyi Guan; Hui Li; Xiaoyu Zeng; Lu Yang; Xiaofang Ding; Xiaoping Fan; Daoxing Chen; Mengtuan Ge (Journal of Fluorescence, 2026)

Corrigendum to “Bavachin induces liver injury and cell apoptosis by targeting Wnt/β-catenin/DRP1 signaling pathway mediated mitochondrial dysfunction” [Toxicol. Lett. 387 (2023) 1–13] - Ying Yang; Wei Zhou; Yihao Wang; Yunxuan Ge; Zheng Fan; Qingquan Liu; Yue Gao (Toxicology Letters, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Enhancing mechanical properties of low-carbon dredged sludge solidification by alkali-activated GGBS-GP systems - Yi Zhou; Jinzhu Zhang; Yucheng Fan; Chen Ge; Zhenglong Zhou; Chuang Feng (Journal of Environmental Chemical Engineering, 2026)

Microplastics drive the reconfiguration of microbial sulfur cycling pathways in seagrass bed sediments - Mingguang Luo; Jinluo Fan; Xiujun Wang; Yibing Ge; Dan Feng; Shengkai Cao; Jun Wang; Hui Deng; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge; Honglin Bu (Environmental Pollution, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

Arbuscular mycorrhizal fungi hypha shape atrazine degradation ability of microbiota by increasing soil aggregation - Yang Sun; Hongyang Pan; Ge Song; Sisi Chen; Alexander V. Kurakov; Fuqiang Song; Jing Wang; Xiaoxu Fan (Mycorrhiza, 2026)

PG-DyMamba: a physics-guided dynamic graph Mamba network for significant wave height prediction - Fan Jiang; Yinzhu Zang; Ruidi Ma; Bo Yu; Hui Li; Song Gao; Yong Ge; Dianjun Ren (Frontiers in Marine Science, 2026)
Accurate prediction of Significant Wave Height (SWH) is vital for marine engineering safety, yet balancing computational efficiency with physical consistency in long-sequence modeling remains a challenge for data-driven approaches. To address this, we propose the Physics-Guided Dynamic Graph Mamba Network (PG-DyMamba). By integrating oceanographic priors such as windwave relations, our Physics-Aware Graph Learner adaptively captures time-varying multivariate dependencies. Concurrently, the Mamba architecture processes long historical sequences with linear complexity. To ensure physical plausibility, the model employs a composite loss function based on energy conservation and fluid smoothness, effectively constraining predictions to adhere to fundamental physical laws. Empirical evaluations on Australia, NDBC, and North Sea datasets confirm that PG-DyMamba outperforms state-of-the-art baselines. Notably, the model achieves a 19.2% MSE reduction in 48-step prediction horizon on the Australia dataset, demonstrating its robustness for operational marine applications.

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Geological sedimentary records constraining Earth-Moon system evolution over the past 60 million years: Insights from Cyclostratigraphy - Zhenwei Ge; Juye Shi; Quanyou Liu; Tailiang Fan; Zhiqian Gao; Huiyuan Xu; Ruyue Wang; Weihui Bi; Zhijun Jin (Gondwana Research, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Processed phellodendri Chinensis cortex attenuates diabetic nephropathy via ferroptosis inhibition through GPX4/SLC7A11/Nrf2/HO-1 signaling pathway - Yue Zhou; Gui Xu; Wenjing Ren; Yang Chen; Shiru Jiang; Shuo Zhang; Xiutong Ge; Hui Gao; Fan Zhang (Journal of Natural Medicines, 2026)

Characterization and genomic analysis of a novel Vibrio harveyi Vibrio phage LRZ - Zhengyu Yang; Hui Ge; Nan Chen; Yongrui Zhang; Huina Wei; Jinbo Hu; Chao Fan; Yilei Wang; Ziping Zhang (Archives of Virology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

YOLO-FR: An enhanced object detector for small object detection in complex scenes - Rui Fan; Renhao Jiao; Weigui Nan; Jin Dang; Zhixue Wang; Xuefeng Ge; Baiying Dong; Xiaoli Luo (Remote Sensing Applications: Society and Environment, 2026)

Tracing molybdenum mineralization through hydrothermal biotite geochemistry in the Jinduicheng porphyry deposit, East Qinling, China - Zhenyu Qin; Fan Yang; Xiaoyu Ge; Leon Bagas; Zhaoyue Ding; Luyang Wang; Lifeng Xu (Journal of Geochemical Exploration, 2026)

Temporal evolution and molecular mechanism of umami peptides in Daweishan Mini chicken: synergistic analysis by peptidomics, molecular docking and molecular dynamics simulation - Shuangmin Liang; Min Yang; Xuehai Ge; Changrong Ge; Jiangping Fan; Zhichao Xiao (Food Chemistry, 2026)

Enabling all-weather interfacial solar evaporation: A latent heat-regulated evaporator with Janus phase change microcapsules - Hailiang Ma; Xinwei Chen; Tiantian Yang; Yuhang Zhang; Linnan Zhang; Fanian Shi; Ge Xu; Jiangtao Fan; Fuxin Liang (Chemical Engineering Journal, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Unraveling the microbiological mechanism of carbon and nitrogen fixation coupling in agricultural soils - Yun Fang; Haoxin Fan; Xiangtian Meng; Juan Wang; Chaorong Ge; Huaiying Yao (Applied Soil Ecology, 2026)

MSI2 expression in single vs. double dominant follicles and its role in Mongolian sheep fecundity - Hao Qinqin; Li Penghui; Zhou Xin; He Yang; Liu Haodong; Li Xiaolong; Yu Mingyang; Zhang Zelin; Fan Jiaxin; Yang Wenchao; Yin Junzhe; Cao Guifang; et al. (Animal Reproduction Science, 2026)

Novel diffusion gradient in thin-films based on antibiofouling Ag/polydopamine membranes for measurement of antibiotics in natural waters - Jiaxing Xie; Fan Ge; Xinyi Yan; Suyu Ren; Yan Wang; Feng Tan (Analytica Chimica Acta, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Mechanistic insights into magnetite-enhanced Indoleacetic acid production by a mixed culture - Yun-Xin Ge; Wei Gao; Zi-Han Fan; Yun Niu; Long-Tao Fang; Xi-Zhen Zou; Wei Zhang (Journal of Water Process Engineering, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Unraveling plant immunity: from pathogen perception to resistance engineering - Fan Liu; Dongdong Ge; Guiwei Lian; Zhifu Han; Jijie Chai (Science China Life Sciences, 2026)

CPE-Pro: A Structure-Sensitive Deep Learning Method for Protein Representation and Origin Evaluation - Wenrui Gou; Wenhui Ge; Yang Tan; Mingchen Li; Guisheng Fan; Huiqun Yu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Simulation of Cutter Wear in Gravel Using a Discrete Element Method Approach - Pei-Yun Shu; Yi-Fan Chen; Tai-Tien Wang; Bin-Chen Benson Hsiung; Chen-Yuan Liao; Louis Ge (Geotechnical and Geological Engineering, 2026)

Impact of Madden–Julian Oscillation on the forecast of marine heatwaves in the southeastern tropical Indian ocean - Zhanxian Cui; Yuanlong Li; Yangke Liu; Qing Bao; Lei Zhang; Kai Ge; Fan Wang (Climate Dynamics, 2026)

Voxel-mirrored homotopic connectivity in upper motor neuron-dominant amyotrophic lateral sclerosis is associated with different spread directions - Jieying Wu; Yingsheng Xu; Tielun Yin; Nan Zhang; Jianqiao Ge; Dongsheng Fan; Shan Ye (Brain Imaging and Behavior, 2026)

Toxicological effects of different particle sizes and types of nano-plastics (NPs) on human lung cells: implications for the health risk of airborne microplastic pollution - Jiayi Fan; Hanbo Li; Mindong Chen; Xuewen Yao; Xinlei Ge; Wankang Chen; Minghan Ouyang; Xiao-San Luo (Air Quality, Atmosphere & Health, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Corrigendum to “Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea” [Lithos 512–513(2025) 108151] - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2026)

Oral administration of egg yolk immunoglobulin (IgY) in Penaeus vannamei to combat against Vp infections - Ge Jiang; Xianping Fan; Jie Cheng; Yi Qiao; Xiaotong Wang; Yijun Liu; Xiaohui Cao; Shen Hui (Journal of Invertebrate Pathology, 2026)

Identification, localization, and bioinformatics analysis of the novel EhSWP12 in Ecytonucleospora hepatopenaei - Xiaohui Cao; Yi Qiao; Tingyue Liu; Huiwen Jiang; Jie Cheng; Ge Jiang; Xianping Fan; Hui Shen (Journal of Invertebrate Pathology, 2026)

Multi-omics reveals taxonomic and functional adaptations of soil microbiota to Bt toxin exposure - Luyao Wang; Ziteng Liang; Jingang Liang; Lei Ge; Lingli Zou; Yixuan Fan; Qinqing Xu; Yin Zhang; Beibei Lv; Kai Zhao; Yunfei Wu; Peng Li (Journal of Hazardous Materials, 2026)

Flux dynamics and scenario simulation of PFAS under extreme hydrological perturbations in urban tributary flowing into the Yangtze River: A focus on floods - Hui Xiao; Ge Tang; Sheng Zhang; Zeqiang Wu; Qi Liu; Shaoyan Feng; Yifan Fan; Tong Liu; Xin Qian; Huiming Li (Journal of Hazardous Materials, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

Enhancement of selective lithium extraction from α-spodumene by autoclaving with NaOH and NaAlO2 at 200–300 °C - Shuhao Dong; Yakai Yang; Hao Zhang; Meiyan Yu; Hui Guo; Ge Kuang; Haidong Wang; Xiaohui Fan (Hydrometallurgy, 2026)

The law of oxidation and exothermic of low-rank coal at critical temperature: Based on the isothermal stage experiment method - Bing Lu; Xun Zhang; Ling Qiao; Cong Ding; Nan Fan; Ge Huang; Fengwei Dai (Fuel, 2026)

Impact of solid-state fermentation using Jiuqu microbiota on dietary fiber of wheat bran and textural properties of whole wheat products - Yaxuan Peng; Ao Wang; Ge Zhang; Rongjia Sun; Haoran Fan; Shiyi Lu; Hongyan Li; Jing Wang; Baoguo Sun (Food Bioscience, 2026)

Multi-species and life-stage patterns of cyanobacterial VOC emissions: Abiotic stress responses and photochemical impacts - Bing Hong; Yinuo Wang; Mengdi Liu; Hao Zhang; Hua Fang; Shutan Ma; Zhijian Fan; Tianyu Hu; Huaiyu Ge; Jian Kang; Jingyi Wang; Xiaoya Zheng; et al. (Environmental Research, 2026)

How the aspect ratio of a rectangular heat source influences convective flow structures: Implications on city-scale heat and pollutants dispersion - Xiaoliang Teng; Yan Zhang; Jindong Wu; Yifan Fan; Jian Ge (Building and Environment, 2026)

Insights into land deformation processes in the Yellow River Delta (China) from synthetic aperture radar interferometry time series and machine learning - Pengfei Ge; Mi Chen; Roberto Tomás; Hui Liu; Kailun Fan; Xi Cheng; Xingyuan Fu; Shuang Wang (Advances in Space Research, 2026)

Generation, transformation and inhibition mechanism of hazardous waste flue coated materials during copper smelting process - Kai Fan; Haipei Zhang; Zhongming Jiang; Songhe Ye; Zhenqin Ge; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Waste Management, 2026)

Retraction notice to “Application of Brachypodium genotypes to the analysis of type II resistance to Fusarium head blight (FHB)” [Plant Sci. 272 (2018) 255–266] - Peisen Su; Xiuxiu Guo; Yanhui Fan; Liang Wang; Guanghui Yu; Wenyang Ge; Lanfei Zhao; Xin Ma; Jiajie Wu; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Science, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Sediment texture induces Fe-S redox zonation and alters microbial assemblages affecting natural attenuation of BDE-47 in upflow columns - Yafen Wang; Jincan Tang; Xiuyuan Fan; Ge He; Nora Fung-Yee Tam (Journal of Hazardous Materials, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Physicochemical controls on Mo mineralisation of the Caosiyao porphyry deposit, northern North China Block - Jialu Song; Fan Yang; Zhenyu Qin; Leon Bagas; Yingjie Li; Xiaoyu Ge; Likun Yang (Journal of Geochemical Exploration, 2026)

Comparative analysis of physicochemical properties and functional characteristics of dielectric barrier discharge plasma-treated chestnut short amylose and animal/plant proteins hybrid nanoparticles - Jie Zhong; Caie Wu; Shengju Ge; Gongjian Fan; Dandan Zhou; Xiaojing Li (Innovative Food Science & Emerging Technologies, 2026)

Synergistic S/Se Co-Doping enables Exceptional microwave absorption in novel graphdiyne composite microspheres - Yihao Fan; Feijie Ge; Longping Huo; Lei Zhang; Zhennan Yue; Baoliang Zhang (Chemical Engineering Journal, 2026)

Sucrose induces simultaneous autolysis attenuation and keratinase production enhancement in Bacillus subtilis WB600 - Yi-Ning He; Dao-Quan Jiao; Ge-Ge Chen; Xiao-Dong Pei; Zhi-Qiang Zhou; Fan Li; Yu-Hui Fang; Cheng-Hua Wang (Bioresource Technology, 2026)

Evaluating permeable pavements' impact on the thermal environment in street canyons through outdoor experiments under hot and humid background climate - Jiahong Zhao; Yifan Fan; Jiang Lu; Xiaoyu Luo; Jian Ge (Building and Environment, 2026)

Mapping vegetation phenology and its response to climate change in Southwest China using solar-induced chlorophyll fluorescence - Feng Tang; Zhongxi Ge; Bohui Tang; Liuyang Fang; Zhen Zhang; Dong Fan; Junyi Chen; Xinming Zhu (Journal of Mountain Science, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Harnessing machine learning for energy optimization and intelligent process control in wastewater treatment - Yibo Du; Tianlong Lei; Jie Jin; Boyu Chen; Xuanbei Wu; Nuan Yang; Yihong Ge; Yan Wang; Qifeng Tan; Dingrui Fan; Yunhui Lei; Ling Yao (Journal of Water Process Engineering, 2025)

Multiomic insights into the regulatory mechanism of anammox consortia: Interspecies cooperation, degradation and self-adaptation to plasticizer stress - Ge-Ge Wu; Jing-Ao Jin; Na-Na Han; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Porous amorphous manganese oxide micro-nanostructures boosted electron transfer between periodate and organic contaminants: The significance of surface reactive oxygen species - Shuyang Deng; Rongyi Ge; Fan Yang; Xiao Guo; Hongrui Xiao; Kangle Lv; Yaobin Ding (Journal of Environmental Chemical Engineering, 2025)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Effect of electron beam irradiation on physicochemical and protein properties of scallop adductor muscles during cold storage - Zhupeng Zhang; Peng Ge; Chaoqi Han; Fan Zhang; Wenxiu Wang; Ran Suo; Qianyun Ma; Zhenzhen Wang; Jianfeng Sun (Food Chemistry, 2025)

Nonlinear rheological behavior and quantitative proteomic analysis of wheat aqueous phase protein at the air-water interface - Zhaoshi Chen; Ge Wang; Runkang Qiu; Peiyao Zhao; Hongjie Ren; Aijun Hu; Bei Fan; Liya Liu; Fengzhong Wang (Food Hydrocolloids, 2025)

Electrospun Baijiu Prolamin based functional nanofiber: Potential in sustainable food preservation - Runkang Qiu; Ge Wang; Peihua Ma; Huanxiang Luo; Bei Fan; Litao Tong; Lili Wang; Yang Zheng; Liya Liu; Fengzhong Wang (Food Packaging and Shelf Life, 2025)

CuFe2O4@T-COF nanosphere-mediated biosensing platform based on DNA walker signal amplification strategy for ultrasensitive HPV detection - Zhen Yu; Yan Zhang; Dongquan Leng; Tingting Wu; Si-Jia Ge; Dawei Fan; Hongmin Ma; Yu Du; Qin Wei (Chemical Engineering Journal, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

Revisiting periodate photoactivation by solar light: Organic contaminant-specific and wavelength-dependent mechanism - Yiping Dong; Rongyi Ge; Hongrui Xiao; Fan Yang; Kangle Lv; Yaobin Ding (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

A Novel Synbiotic Protects Against DSS-Induced Colitis in Mice via Anti-inflammatory and Microbiota-Balancing Properties - Yong Yang; Yuyu Qiao; Ge Liu; Weihao Chen; Ting Zhang; Jing Liu; Weiping Fan; Mingwei Tong (Probiotics and Antimicrobial Proteins, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Statistical inferences of differences and correlations in the seismic frequencies of large-scale fault zones in Western Sichuan, China - Yuan Xue; Dan Hu; Junreng Ge; Xinyu Yao; Mingyue Dai; Bingyan Fan; Yu Ming; Muchen Lin (Journal of Seismology, 2025)

Leptin drives glucose metabolism to promote cardiac protection via OPA1-mediated HDAC5 translocation and Glut4 transcription - Fan Yang; Youfu He; Ling Zhao; Jing Huang; Fawang Du; Shui Tian; Yang Zhang; Xinghui Liu; Baolin Chen; Junhua Ge; Zhi Jiang (Functional & Integrative Genomics, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Carbon stabilization by iron plaque on rice roots: The role of oxygen loss - Liang Wei; Xuechi Rong; Hongzhao Yuan; Yongfu Li; Xiaorong Fan; Ning Ling; Zhenke Zhu; Bahar S. Razavi; Yakov Kuzyakov; Pil Joo Kim; Jianping Chen; Tida Ge (Soil Biology and Biochemistry, 2025)

The fungicide jinggangmycin stimulates fecundity of Nilaparvata lugens Stål via ILP/Foxo signaling - Xudong Zhao; Yuting Ding; Zhirou Duan; Di Deng; Zhiyue Mao; Yan Zhu; Xiaoxi Fan; Guohui Yu; Linquan Ge (Pesticide Biochemistry and Physiology, 2025)

Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2025)

Quantify coupling effects between outdoor microclimate and building energy consumption for BIPV buildings in different local climate zones - Mengyi Huang; Yichen Chen; Jindong Wu; Xiaoyu Luo; Yifan Fan; Jian Ge (Energy and Buildings, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

Influence of overlooked environmental factors on analytical accuracy in hygrothermal response of building envelopes based on the coupled heat and moisture transfer theory - Tao Gao; Ye Guo; Weilan Wu; Jian Ge; Yifan Fan; Jiang Lu; Yucong Xue (Building and Environment, 2025)

The improvement of wind comfort and natural ventilation in high-rise building vertical gardens with adjustable louver angles - Xiaoliang Teng; May Lwin Oo; Jian Ge; Nyuk Hien Wong; Yifan Fan (Building and Environment, 2025)

Co-encapsulation of an AKT Inhibitor Enhances the Tumor-cell Selectivity of STING Agonists in Co-delivery Liposomes - Ziyu Ge; Qiang Zhang; Yuming Wang; Lin Miao; Xinqi Wang; Ni Fan; LiLi Duan; Yunfei Li; Xue-Jie Qi (Pharmaceutical Research, 2025)

Optimizing blood–brain barrier permeability: the effect of wine processing on alkaloids in Phellodendri Chinensis Cortex - Shuo Zhang; Jiahui Zhao; Wenjing Ren; Yue Zhou; Yang Chen; Shiru Jiang; Gui Xu; Xiutong Ge; Hui Gao; Fan Zhang (Journal of Natural Medicines, 2025)

Mitomycin C-induced prophage activation for exploring the Lysogeny-lysis functional dynamics in situ - Ruoyi Xu; Tida Ge; Yuchuan Fan; Lu Yang; Ying Zhang; Siqin Han; Mark Radosevich; Xiaolong Liang (Applied Soil Ecology, 2025)

A constrained multi-objective evolutionary algorithm for multi-class instance selection - Qijun Wang; Yujie Ge; Lei Zhang; Fan Cheng (Swarm and Evolutionary Computation, 2025)

Pollen-vegetation-climate relationships in different steppe types of North China: implications for Quaternary reconstructions of vegetation and climate - Yongjie Zhao; Fan Xu; Sidan Cui; Xin Mao; Gaolei Jiang; Ruchun Zhang; Linjing Liu; Yawen Ge; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Climate change reshapes rice geographical indications in China: Opportunities and challenges of rural revitalization - Xinyi Fan; Zhixin Hao; Quansheng Ge (Journal of Cleaner Production, 2025)

Mineral prospectivity prediction from airborne magnetic data based on the RPCA-ResNet hybrid learning framework - Zhenyu Fan; Shengqing Xiong; Tengfei Ge; Jingzi He; Xue Yang; Yao Liu; Jianfu Luo (Journal of Asian Earth Sciences, 2025)

Fabrication of bifunctional gold nanoparticles for self-calibration UV–Vis/surface-enhanced Raman spectroscopy dual-mode analysis of Hg2+ in milk - Jinxin Chen; Zhihong Wang; Miao Ding; Ying Gu; Kun Ge; Xuejing Fan (Food Chemistry, 2025)

PM2.5 promotes platelet activation and thrombosis via ROS/MAPKs pathway-mediated mitochondrial dysfunction - Yuquan Xie; Dongxia Fan; Biao Wu; Jianshu Guo; Ge Wang; Lu Yu; Chihang Zhang; Jinzhuo Zhao; Si Zhang (Environmental Research, 2025)

Development and evaluation of photolysis and gas-phase reaction scheme in EPICC-model: Impacts on tropospheric ozone simulation - Wending Wang; Huansheng Chen; Zifa Wang; Jie Li; Xueshun Chen; Fenfen Yu; Xiaohan Fan; Shuman Zhao; Bo Hu; Wei Wang; Xiao Tang; Zhe Wang; et al. (Atmospheric Environment, 2025)

Correction: A Novel Synbiotic Protects Against DSS-Induced Colitis in Mice via Anti-inflammatory and Microbiota-Balancing Properties - Yong Yang; Yuyu Qiao; Ge Liu; Weihao Chen; Ting Zhang; Jing Liu; Weiping Fan; Mingwei Tong (Probiotics and Antimicrobial Proteins, 2025)

Regulating factors and spatiotemporal patterns of terrestrial dissolved organic carbon adsorption in a high-turbidity estuary - Zhi Chen; Ricardo Torres; Jialing Yao; Ding He; Daidu Fan; Daniel Conley; Andrew Manning; Jianzhong Ge (Water Research, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Effects of mulches on greenhouse gas emissions and soil microbial communities in cabbage production - Rong Liang; Lei Mei; Xuelian Fan; Jiangxing Wu; Mouliang Xiao; Yongfu Li; Jina Ding; Li Wang; Jaloliddin Shavkiev; David R. Chadwick; Davey Jones; Zhaofeng Yuan; et al. (Journal of Hazardous Materials, 2025)

TAM-TR: Text-guided attention multi-modal transformer for object detection in UAV images - Jianhao Xu; Xiangtao Fan; Hongdeng Jian; Chen Xu; Weijia Bei; Qifeng Ge; Teng Zhao; Ruijie Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Comparison of protein composition and structural characterization of prolamin from Jiuzao extracted with different alkaline-alcohol methods - Ge Wang; Xinran Dai; Zhaoshi Chen; Runkang Qiu; Aijun Hu; Jie Zheng; Yang Zheng; Siyao Xue; Bei Fan; Liya Liu; Fengzhong Wang (Food Chemistry, 2025)

Engineered flower-shaped MXene-copper nanowire composite facilitate mechanically tuned and sensitive field-effect transistors in miniaturized portable devices toward noninvasive NSCLC prognostic monitoring - Chengling Zhao; Bing Xia; Zhao Jin; Zhenkai Fan; Qiao Ge; Haining Hong; Haiwei Sang; Lixiang Li; Ansheng Wang (Chemical Engineering Journal, 2025)

Dissolved organic matter derived from long-term photodegradation of plastics alters microbial methane conversion in mangrove sediments - Minmin Wang; Leiqian Ma; Derong Zhang; Fan Yang; Xing Yang; Bin Wang; Xue Li; Chengjun Ge; Jiwei Luo; Ying Zhang (Bioresource Technology, 2025)

MultiKD-DTA: Enhancing Drug-Target Affinity Prediction Through Multiscale Feature Extraction - Riqian Hu; Ruiquan Ge; Guojian Deng; Jin Fan; Bowen Tang; Changmiao Wang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Deciphering the influence of heavy metals on adverse cardiovascular events using machine learning - Guanmou Li; Tong Zhang; Kunyang He; Miao Zhang; Jinlin Hu; Teng Ge; Meng Wang; Rongjun Zou; Xiaoping Fan (Toxicology Letters, 2025)

Hidden risk of microplastics in milk tea and coffee: A case study from China's freshly-made beverage market - Hongbo Su; Ge Tang; Jianing Shen; Qi Liu; Wanlu Xu; Xin Qian; Yifan Fan (Journal of Hazardous Materials, 2025)

Improvement of carbon peaking path in the construction sector in medium-sized cities: A case study of Zhangzhou city, China - Jian Ge; Qingqing Miao; Jianya Xiao; Shuang Yu; Jiang Lu; Yifan Fan; Xiaoyu Luo (Journal of Cleaner Production, 2025)

The influence of mineralogical characteristics and pH on uranium extraction via in-situ leaching: Preliminary case analysis of the Hadatu uranium deposit, China - Peng Qiao; Shengqing Xiong; Liangquan Ge; Hao Song; Huijie Yu; Yihan Yang; Ruyi Wang; Shihu Kang; Yiru Zhou; Yuanqing Fan (Hydrometallurgy, 2025)

Transcriptome analysis reveals the molecular mechanisms of the 8-day infection cycle of Ecytonucleospora hepatopenaei in Litopenaeus vannamei and the host's molecular responses - Yan Rong; Yi Qiao; Tingyue Liu; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Xianping Fan; Hui Shen (Fungal Biology, 2025)

Fungal xylomannan as a dietary supplement: Activates hepatic AMPK/HIF1α signaling to attenuate insulin resistance - Yuhan Meng; Xiushi Jia; Lujuan Zheng; Min Wang; Jing Xia; Mingming Li; Junzhu Wei; Yanchen Qi; Chen Meng; Jiaxing Sheng; Pengyu Ge; Yuying Fan; et al. (Food Bioscience, 2025)

From lab to plant: Process design and scalability challenges in MgH2 synthesis - Ge Gao; Zhendong Yao; Jing Gu; Jiaxing Xie; Chao Li; Meiqiang Fan; Xuezhang Xiao; Lixin Chen (Chemical Engineering Journal, 2025)

Inhalation dominates exposure of expired particles in close contact with head movement - Yinshuai Feng; Yuguo Li; Yifan Fan; Jian Ge (Building and Environment, 2025)

Root exudates and microbial metabolites: signals and nutrients in plant-microbe interactions - Xiaoyan Fan; An-Hui Ge; Shanshan Qi; Yuefeng Guan; Ran Wang; Nan Yu; Ertao Wang (Science China Life Sciences, 2025)

Targeting adenosine A2A receptors for early intervention of retinopathy of prematurity - Xuhao Chen; Xiaoting Sun; Yuanyuan Ge; Xuzhao Zhou; Jiang-Fan Chen (Purinergic Signalling, 2025)

Deep plowing enhanced soil nematode communities and soil quality in dryland wheat fields on the Loess Plateau of China - Yuejing Qiao; Duo Gao; Yaqi Fan; Lijing Zhang; Qiuyan Yan; Laichun Guo; Junyong Ge; Tingmiao Huang (Agriculture, Ecosystems & Environment, 2025)

Characterization of Enterocytozoon hepatopenaei infection stages in shrimp using machine learning and gene network analysis - Yi Qiao; Leiting Zhang; Xiaohui Cao; Tingyue Liu; Huiwen Jiang; Jie Cheng; Ge Jiang; Xianping Fan; Hui Shen (Journal of Invertebrate Pathology, 2025)

An in-depth study of the growth inhibition of Vibrio parahaemolyticus by Surfactin and its effects on cell membranes, ROS levels and gene transcription - Zijie Zhou; Luoping Xiang; Xiaotong Wang; Ge Jiang; Jie Cheng; Xiaohui Cao; Xianping Fan; Hui Shen (Journal of Invertebrate Pathology, 2025)

Quorum sensing-mediated microecological homeostasis in anammox consortia - Jia-Hui Yang; Dong-Qi Huang; Ge-Ge Wu; Na-Na Han; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Colonization time of plastisphere drives the dynamics of organic carbon stability and microbial communities in seagrass bed sediments - Shuailing Hou; Jun Wang; Dan Feng; Dongming Wu; Shiquan Chen; Jinluo Fan; Mingguang Luo; Hui Deng; Xing Yang; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge (Journal of Hazardous Materials, 2025)

Combined exposure of sleep deprivation and environmental particulate matter drives aging in multiple systems - Lu Yu; Chihang Zhang; Biao Wu; Jianshu Guo; Dongxia Fan; Ge Wang; Wenqing Zhang; Lin Lin; Xinlei Xu; Xihao Du; Xiao-yong Zhang; Yuquan Xie; et al. (Journal of Hazardous Materials, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Differential size-dependent response patterns and antibiotic resistance development mechanism in anammox consortia - Na-Na Han; Jun-Hui Yang; Ge-Ge Wu; Jia-Hui Yang; Jing-Ao Jin; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Two-stage multi-objective optimization of solar roof design for railway-station represented large-space public buildings considering thermal efficiency, carbon emissions, and daylighting - Biqiu Ge; Zhengyu Fan; Jiaping Liu (Building and Environment, 2025)

Seismic performance of multiple hardening wall: macro-element modelling, parametric analysis, and design - Hongbo Jiang; Haotian Liu; Tong Guo; Guangzhong Fan; Jian Sun; Hongxing Qiu; Wenjie Ge; Yanqing Xu; Kongyang Chen; Chunchao Chen (Bulletin of Earthquake Engineering, 2025)

Biological interactions and soil properties shape bacterial and fungal communities during restoration of Pinus thunbergii shelter in saline soils - Zhugui Wen; Xinyu Liu; Wei Zhou; Xinke Liu; Zhaohan Fan; Yuxuan Wang; Boping Tang; Baoming Ge (Antonie van Leeuwenhoek, 2025)

Auxiliary optimization framework based on scaling transformation matrix for large-scale multi-objective problem - Yuanyuan Ge; Zhanpeng Wang; Hongyan Wang; Fan Cheng; Lei Zhang (Swarm and Evolutionary Computation, 2025)

Pathways of south-derived iodine-129 intrusion into Tibet as revealed by its spatial distribution - Yukun Fan; Peng Cheng; Jie Zhou; Yanyun Wang; Weijian Zhou; Qi Liu; Luyuan Zhang; Huan Jiang; Ge Xu; Ning Chen; Xiaolin Hou (Journal of Hazardous Materials, 2025)

Dual stabilization, phase inversion and mechanical properties of a novel bigels system based on myofibrillar protein hydrogel and glycerol monostearate oleogel - Lixian Zhang; Zhenzhen Ge; Lihua Zhang; Wei Zong; Wen Fan (Journal of Food Engineering, 2025)

Unraveling the ecological interactions between dairy strains Bacillus licheniformis and Bacillus cereus during the dual-species biofilm formation - Yang Liu; Wenwen Ge; Yuxin Sun; Hongchao Dai; Luyao Fan; Lei Yuan; Zhenquan Yang; Xinan Jiao (Food Microbiology, 2025)

Synergic solar interfacial evaporation with heterogenous electro-Fenton: A near zero-discharge approach for water purification - Xinfei Fan; Xiaoyu Liu; Xingzu Zhang; Yanbin Xin; Yuanlu Xu; Hongli Ge; Yanming Liu (Chemical Engineering Journal, 2025)

Spatial-temporal variations of kelp 129I contents in coastal waters of China before and after the Fukushima Daiichi Nuclear Power Plant accident - Xiaowen Liu; Jialin Liu; Yukun Fan; Guozhi Xie; Xiaole Sun; Luyuan Zhang; Qi Liu; Xiaoqi Yang; Delin Duan; Fangli Qiao; Chang Zhao; Baozhu Ge; et al. (Marine Pollution Bulletin, 2025)

Global warming likely compromises the annual performance of zero-energy buildings while the urban heat island effect exacerbates the impact - Yiman Zhao; Xiaotian Ding; Yifan Fan; Yongling Zhao; Jian Ge; Jan Carmeliet (Sustainable Cities and Society, 2025)

Stratified distribution of recycled components in the mantle of the South China Sea unveiled through magnesium isotopes - Zhen-Min Ge; Xiao-Long Huang; Fan Yang; Yang Yu; Guan-Hong Zhu; Le Zhang; Yu-Xin Cai; Guo-Hong Sun (Chemical Geology, 2025)

An improved U-Pb dating method for carbonates via LA-SF-ICP-MS mapping and its applications - Lili Gui; Xuesong Lu; Fangyue Wang; Can Ge; Lin Jiang; Shaobo Liu; Wuren Xie; Weiyan Chen; Junjia Fan; Hai Wu; Saijun Wu; Yingying Wang; et al. (Science China Earth Sciences, 2025)

Corrigendum to “Application of Brachypodium genotypes to the analysis of type II resistance to Fusarium head blight (FHB)” [Plant Sci. 272 (2018) 255–266] - Peisen Su; Xiuxiu Guo; Yanhui Fan; Liang Wang; Guanghui Yu; Wenyang Ge; Lanfei Zhao; Xin Ma; Jiajie Wu; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Science, 2025)

Optimization and identification of key process parameters for in-situ leaching of uranium in the Barun uranium deposit, China - Peng Qiao; Yuanqing Fan; Shengqing Xiong; Liangquan Ge; Yixuan Yao; Ruyi Wang; Hao Song; Huijie Yu; Xiaoping Ren; Zengjie Gui (Ore and Energy Resource Geology, 2025)

Large-scale metabolomic landscape of edible maize reveals convergent changes in metabolite differentiation and facilitates its breeding improvement - Chunhui Li; Zhiyong Li; Baishan Lu; Yaxing Shi; Senlin Xiao; Hui Dong; Ruyang Zhang; Hui Liu; Yanyan Jiao; Li Xu; Aiguo Su; Xiaqing Wang; et al. (Molecular Plant, 2025)

Sewage treatment effect of MPSRs under different influent NH4+-N concentrations and its mechanism of nitrogen removal - Ge Yu; Guo Shen; Liyuan Zhao; Wanying Liu; Wenbin Zhao; Fan Wang; Shengshu Ai; Dejun Bian; Donglei Zou (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Effect of NaCl concentration on the interfacial and foaming properties of wheat aqueous phase protein - Zhaoshi Chen; Ge Wang; Muyuan Zhao; Peiyao Zhao; Runkang Qiu; Bei Fan; Aijun Hu; Liya Liu; Fengzhong Wang (Food Hydrocolloids, 2025)

Identification and spatial distribution of organophosphorus flame retardants in surface soils from typical petrochemical industry and flame retardant production parks in China - Zhiyong Fan; Chaoyang Long; Xiang Ge; Zhaofa Huang; Helong Ren; Yingxin Yu; Taicheng An (Environmental Pollution, 2025)

Retraction notice to “Multi-scale experimental investigation on the fluidization of Geldart B 13X zeolite particles: A comprehensive dataset for CFD validation” [Chem. Eng. J. 471 (2023) 144724] - Mingming Ge; Hang Zhou; Avinash Vaidheeswaran; William Rogers; Dixia Fan; Cheng Li (Chemical Engineering Journal, 2025)

Modeling diabetic cardiomyopathy using human cardiac organoids: Effects of high glucose and lipid conditions - Xiangyu Wang; Xin Tan; Ting Zhang; Shuai Xu; Yiyao Zeng; Anchen Xu; Xian Li; Ge Zhang; Yufeng Jiang; Hezi Jiang; Jili Fan; Xiaohong Bo; et al. (Chemico-Biological Interactions, 2025)

Lifetime exposure to health-related air pollutants in the United Kingdom: A spatiotemporal evaluation (1930–2010) through WRF-CMAQ modeling - Ge Chen; Yiming Liu; Haofan Wang; Menghe Wang; Lan Chen; Hejun Hu; Shiyu Zhang; Baozhuo Ai; Miao Cai; Zilong Zhang; Qi Fan; Hualiang Lin (Atmospheric Environment, 2025)

Temperature effects on SOA formation of n-dodecane reaction initiated by Cl atoms - Cici Fan; Weigang Wang; Ke Wang; Ting Lei; Wang Xiang; Chunyan Hou; Junling Li; Yucong Guo; Maofa Ge (Atmospheric Environment, 2025)

The response mechanisms of kelp Macrocystis pyrifera holobiont to elevated temperature and CO2 concentration - Tianle Xi; Yajing Liu; Xiaowen Zhang; Shanshan Ge; Yitao Wang; Ke Sun; Xiao Fan; Dong Xu; Pengyan Zhang; Chengwei Liang; Naihao Ye (Journal of Applied Phycology, 2025)

Seasonal variations in the transpiration-to-evapotranspiration ratio and their driving forces in China’s terrestrial ecosystem during 1981–2021 - Bin Wang; Zhongen Niu; Lili Feng; Na Zeng; Rong Ge; Jiayi Fan (Journal of Geographical Sciences, 2025)

Alpha-Momorcharin, a type I ribosome inactivating protein, induced apoptosis of hepatocellular carcinoma SK-HEP-1 cells through mitochondrial pathway - Di Yang; Di Peng; Yiping Zhou; Zihao Qiang; Li Wan; Xiang Fan; Yanfa Meng; Ge Xu; Yao Meng (Natural Product Research, 2025)

Genome-wide identification, evolution, diversity and expression of Caspase gene family in Haliotis discus hannai - Yuping Chen; Wangying Wu; Hui Ge; Zhen Zhao; Hanling Gan; Nan Chen; Jianpeng Huang; Chao Fan; Mingyi Cai; Yilei Wang; Ziping Zhang (Aquaculture, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

Accumulation characteristics and fate modeling of phthalic acid esters in surface water from the Three Gorges Reservoir area, China - Shuai Sun; Bing Zhang; Junjie Hu; Wen Gu; Zhen Wang; Deling Fan; Feng Ge; Lili Shi; Lei Wang (Journal of Environmental Sciences, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Rice straw nitrogen can be utilized by rice more efficiently when co-incorporating with milk vetch - Qianyu Fan; Jiancheng Xie; Jintao Du; Huanyu Ge; Cuilan Wei; Hao Qian; Hai Liang; Jun Nie; Feng Hu; Songjuan Gao; Weidong Cao (European Journal of Agronomy, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

The structure–activity relationship for CO2 absorption heat of chain diamines: Effects of amino types, methyl/ethyl groups, and chain lengths - Xi Tang; Ge Gao; Wufeng Jiang; Bin Xu; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Quaternary ammonium chitosan-functionalized mesoporous silica nanoparticles: A promising targeted drug delivery system for the treatment of intracellular MRSA infection - Junfeng Liu; Liying Zhang; Haodi Ma; Haoyang Sun; Shu-ai Ge; Jieyi Liu; Shengdi Fan; Chunshan Quan (Carbohydrate Polymers, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Large-scale rice mapping under spatiotemporal heterogeneity using multi-temporal SAR images and explainable deep learning - Ji Ge; Hong Zhang; Lijun Zuo; Lu Xu; Jingling Jiang; Mingyang Song; Yinhaibin Ding; Yazhe Xie; Fan Wu; Chao Wang; Wenjiang Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Influence of biodegradable microplastics on soil carbon cycling: Insights from soil respiration, enzyme activity, carbon use efficiency and microbial community - Dan Song; Guoqin Jin; Ziqi Su; Chaorong Ge; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

Bt toxins alter bacterial communities and their potential functions in earthworm intestines - Luyao Wang; Yixuan Fan; Lingli Zou; Lei Ge; Wei Jiang; Shengqian Chao; Beibei Lv; Kai Zhao; Jun Chen; Peng Li (Environmental Pollution, 2025)

An improved method to accelerate the acquisition efficiency of the T1-T2 spectrum based on the IR-BSSFP-CPMG pulse sequence∗ - Fu Zuo; Xinmin Ge; Lanchang Xing; Bohan Wu; Yiren Fan; Jackson Jervis Junior; Bin Wang (Computers & Geosciences, 2025)

Engineering the microenvironment in Ba-doped Fe catalyst with alkali metal promoters for enhanced CO2 hydrogenation to α-olefins - Joshua Iseoluwa Orege; Yang Yu; Jian Wei; Qixin Fan; Jixin Zhang; Lifei Song; Qingjie Ge; Jian Sun (Chemical Engineering Journal, 2025)

Highly efficient CO2 capture from open air and dilute gas streams by tunable azolate ionic liquids based deep eutectic solvents - Guokai Cui; Yepin Cheng; Wei Zhang; Xiangyu Shen; Lai Li; Ruina Zhang; Yaoji Chen; Quanli Ke; Chunliang Ge; Huayan Liu; Wenyang Fan; Hanfeng Lu (Chemical Engineering Journal, 2025)

Influences of urban shape on city-scale heat and pollutants dispersion under calm and moderate background wind condition - Yan Zhang; Yifan Fan; Jian Ge (Building and Environment, 2025)

Resuspension of surface particles from the free-fall package: A chamber study - Ke Xu; Yinshuai Feng; Jindong Wu; Yifan Fan; Jian Ge (Building and Environment, 2025)

Influences of permeable pavements with different hydraulic properties on evaporative cooling and outdoor thermal environment: Field experiments - Jiahong Zhao; Jiang Lu; Jian Ge; Yifan Fan; Haoxian Wang; Muye Gu; Yucong Xue; Yujie Zhao; Guoquan Lv; Haiqin Lin; Kang Zhao; Xiaoyu Luo (Building and Environment, 2025)

Enhanced visual detection of litchi fruit in complex natural environments based on unmanned aerial vehicle (UAV) remote sensing - Changjiang Liang; Juntao Liang; Weiguang Yang; Weiyi Ge; Jing Zhao; Zhaorong Li; Shudai Bai; Jiawen Fan; Yubin Lan; Yongbing Long (Precision Agriculture, 2025)

CmERFⅠ-5 and CmERFⅤ-2 affect ethylene synthesis and sucrose accumulation in postharvest oriental melon fruit at low temperature - Fan Yang; Ge Gao; Cheng Wang; Jingyue Guan; Junqin Chen; Hongyan Qi (Postharvest Biology and Technology, 2025)

Force decomposition of vortex–plate interaction via dynamic mode decomposition - Dehan Yuan; LinLin Kang; Guangmin Dai; Mingming Ge; Dixia Fan (Ocean Engineering, 2025)

Assessment of the interaction between digital infrastructure and ecological resilience: Insights from Yangtze River Delta Urban Agglomeration in China - Qiangyi Li; Jiexiao Ge; Xinmin Zhang; Xiaoyu Wu; Houbao Fan; Lan Yang (Journal of Cleaner Production, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Parametric study on the methanol/diesel JCCI mode with dual-direct injection system in a light-duty engine - Bo Li; Wei Tan; Yunpeng Wei; Liyun Fan; Yang Wang; Xianyin Leng; Ge Xiao; Wuqiang Long (Fuel, 2025)

XGBoost algorithm-guided synthesis of violet phosphorus/MoAlB-MBene nanozyme for portable wireless intelligent sensing of sesamol in different varieties of sesame seeds - Tao Chen; Peng Liu; Yu Ge; Xiaoting Lei; Zhenzong Fan; Xiaoyu Zhu; Yangping Wen; Hassan Karimi-Maleh; Xiaoqiang Wang (Chemical Engineering Journal, 2025)

Visible light-activated Ti-MOF loaded metformin-hydrogel composite dressing for accelerated chronic diabetic wound healing - Meng Tian; Chuan Fan; Rujiao Ge; Guodong Liu; Lei Su; Haifeng Dong (Chemical Engineering Journal, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

Holocene pollen records from a large shallow lake in East Asia: Complexity of climate changes, environmental variations, and human activities - Changhong Liu; Yawen Ge; Yuecong Li; Gaihui Shen; Xiaolan Yang; Zijing She; Baoshuo Fan; Huiyuan Jia (CATENA, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Response of Ceratophyllum demersum L. and its epiphytic biofilms to 6PPD and 6PPD-Q exposure: Based on metabolomics and microbial community analysis - Xiang Li; Weitao Liu; Yichen Ge; Ruiying Shi; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Qi Wang; Jianling Wang; Fan Mo; Aurang Zeb; Miao Yu (Journal of Hazardous Materials, 2024)

High-affinity potassium transporter TaHAK1 implicates in cesium tolerance and phytoremediation - Jin Liu; Shuai-Bo Chen; Ze-Hua Fan; Haitao Liu; Yinglong Chen; Chandra Shekhar Seth; Evgenios Agathokleous; Tian-Cai Guo; Guo-Zhang Kang; Ge-Zi Li (Journal of Hazardous Materials, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

Study on the reactions of n-pentanal and n-hexanal with Br atoms: Kinetics, gas-phase products, and SOA formation - Cici Fan; Huijie Yan; Weigang Wang; Zheng Sun; Maofa Ge (Atmospheric Environment, 2024)

Grain size of Quaternary sediments in the continental shelf-margin: implications for paleo-environment in the Northwestern South China Sea - Jiawang Ge; Qingping Li; Xiaoming Zhao; Weixin Pang; Qi Fan; Xiang Cheng; Xin Zhang (Frontiers in Marine Science, 2024)
Introduction The quantitative distribution of grain size of sediments could imply the hydrodynamic conditions as well as terrestrial material composition; and thus, it is indicative of sea-level fluctuations, regional sources and climate changes. The environmentally sensitive components extracted from grain size data serve as excellent indicators of the sedimentary environment and monsoon intensity. Material and methods The drilling data from the shelf margin of the northwestern Qiongdongnan Basin provide an excellent opportunity for studying hydrodynamics and climate change in the Quaternary South China Sea (SCS). The 49 obtained samples of Quaternary sediments are primarily composed of clay and silt, with a low sand content. The environmentally sensitive components are extracted from the sediment samples, based on multiple attempts including grain size-standard deviation, the end-member modelling analysis and the principal component factor analysis methods. Results The increased grain size as supplemented by ratios of rolling movement on the sediment probability accumulation curves indicate enhanced hydrodynamic conditions in the Quaternary northwestern SCS. The alternative indicators of the Quaternary East Asian monsoon are obtained after a comprehensive comparative analysis. The changes in the content of the grain size components of 5.21-6.72 μm and 27.4-35.3 μm are used as the proxy indicators for the Quaternary East Asian summer and winter monsoon of the NW-SCS, respectively. It is likely indicated that the East Asian winter monsoon remarkably strengthened since 1.3 Ma but reached its maximum intensity around 0.8 Ma. During this period, the magnitude of both climatic temperature and sea-level fluctuations are significant, thus, the coarse-grained component increased at falling or low sea-level stages. Discussion The grain size characteristics of the Quaternary shelf margin sediments are indicative of hydrodynamic conditions, source-sink systems and environmental monsoon climate changes in the northwestern SCS.

The Controlling Factors and Prediction of Deep-Water Mass Transport Deposits in the Pliocene Qiongdongnan Basin, South China Sea - Jiawang Ge; Xiaoming Zhao; Qi Fan; Weixin Pang; Chong Yue; Yueyao Chen (Journal of Marine Science and Engineering, 2024)
Large-scaled submarine slides or mass transport deposits (MTDs) widely occurred in the Pliocene Qiongdongnan Basin, South China Sea. The good seismic mapping and distinctive topography, as well as the along-striking variation in sediment supply, make it an ideal object to explore the linkage of controlling factors and MTD distribution. The evaluation of the main controlling factors of mass transport deposits utilizes the analysis of terrestrial catastrophes as a reference based on the GIS-10.2 software. The steepened topography is assumed to be an external influence on triggering MTDs; therefore, the MTDs are mapped to the bottom interface of the corresponding topography strata. Based on detailed seismic and well-based observations from multiple phases of MTDs in the Pliocene Qiongdongnan Basin (QDNB), the interpreted controlling factors are summarized. Topographic, sedimentary, and climatic factors are assigned to the smallest grid cell of this study. Detailed procedures, including correlation analysis, significance check, and recursive feature elimination, are conducted. A random forest artificial intelligence algorithm was established. The mean value of the squared residuals of the model was 0.043, and the fitting degree was 82.52. To test the stability and accuracy of this model, the training model was used to calibrate the test set, and five times 2-fold cross-validation was performed. The area under the curve mean value is 0.9849, indicating that the model was effective and stable. The most related factors are correlated to the elevation, flow direction, and slope gradient. The predicted results were consistent with the seismic interpretation results. Our study indicates that a random forest artificial intelligence algorithm could be useful in predicting the susceptibility of deep-water MTDs and can be applied to other study areas to predict and avoid submarine disasters caused by wasting processes.

Observational study of microphysical and chemical characteristics of size-resolved fog in different regional backgrounds in China - Panyan Ge; Yun Zhang; Shuxian Fan; Yuan Wang; Haopeng Wu; Xinyi Wang; Sirui Zhang (Science of The Total Environment, 2024)

Reconstructing the rapid transitions of ecosystems during the mid-late Holocene: A pollen record from Haixing wetland in Bohai Bay, North China - Yihang Cao; Yawen Ge; Siyu Wang; Baoshuo Fan; Changhong Liu; Hanfei You; Rongrong Wang; Ying Wang; Zhen Zhang; Shengrui Zhang; Cange Li; Yuecong Li (Quaternary Science Reviews, 2024)

New insights into the functional group influence on CO2 absorption heat and CO2 equilibrium solubility by piperazine derivatives - Xi Tang; Bin Xu; Wufeng Jiang; Xiaoshan Li; Ge Gao; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2024)

Evaluating drought stress response of poplar seedlings using a proximal sensing platform via multi-parameter phenotyping and two-stage machine learning - Xuexing Fan; Huichun Zhang; Lei Zhou; Liming Bian; Xiuliang Jin; Luozhong Tang; Yufeng Ge (Computers and Electronics in Agriculture, 2024)

A WRF-UCM-SOLWEIG framework for mapping thermal comfort and quantifying urban climate drivers: Advancing spatial and temporal resolutions at city scale - Xiaotian Ding; Yongling Zhao; Dominik Strebel; Yifan Fan; Jian Ge; Jan Carmeliet (Sustainable Cities and Society, 2024)

Optimization framework for daylight and thermal environment of retractable roof natatoriums based on generative adversarial network and genetic algorithm - Zhongqi Yu; Xinyi Ge; Zhaoxiang Fan; Yihang Zhou; Dawei Lin (Energy and Buildings, 2024)

Impact of urban form on building energy consumption in different climate zones of China - Yiman Zhao; Xiaotian Ding; Ziyu Wu; Shi Yin; Yifan Fan; Jian Ge (Energy and Buildings, 2024)

Study on the regulation of droplet motion behavior on superhydrophobic surfaces - Shiya Gu; Hongcheng Ge; Hengyi Wei; Yuanyuan Sun; Tianyi Zhang; Huan Wang; Liyan Wu; Xiaoguang Fan (Chemical Engineering Journal, 2024)

Micro-structure design of black ceramic composite surface towards photothermal superhydrophobic anti-icing - Yihan Zhang; Xiaoqiang Fan; Xinrui Li; Zhongpan Zhang; Yuxuan Zhang; Zhipeng Chen; Siyi Ge; Yunsong Wang; Minhao Zhu (Chemical Engineering Journal, 2024)

Synergistic metabolism intervention and immune activation for antitumor therapy by biomineralized lactate oxidase - Yuxuan Ge; Zixin Wang; Yujia Lu; Fan Rong; Bin Hao; Zhao Li; Junsheng Chen; Yin Wang (Chemical Engineering Journal, 2024)

A hollow mesoporous iron oxide nanoparticle to strengthen Fenton reaction and weaken antioxidant defense systems for high efficacy tumor ferroptosis therapy - Jing Yang; Jiaoyang Zhu; Bin Ren; Haobin Cai; Zongheng Li; Qingdeng Fan; Wei Xiong; Jie Feng; Chenggong Yan; Ge Wen; Yan Li; Chaomin Chen; et al. (Chemical Engineering Journal, 2024)

Etiological study on forest fire accidents using Bow-tie model and Bayesian network - Shi-yi Li; Xin Li; Fu-qiang Yang; Fan-liang Ge (Natural Hazards, 2024)

Improving the sustainability of milk production across different climate regions in China - Zhaoping Wu; Yuanyuan Du; Guofu Yang; Linshan Lin; Xiaoyu Hou; Yandong Tan; Xing Fan; Yuan Ren; Bijie Wu; Shun Liu; Scott X. Chang; Wanhong Sun; et al. (Sustainable Production and Consumption, 2024)

Cyanobacterial blooms in Lake Taihu: Temporal trends and potential drivers - Ting Song; Hujun Zhang; Yanjuan Xu; Ximing Dai; Fan Fan; Yu Wang; Ge Liu (Science of The Total Environment, 2024)

The chelation mechanism of neonicotinoid insecticides influencing cadmium transport and accumulation in rice at different growth stage - Qiongfang Ouyang; Na Liu; Zhaoxia Fan; Feng Li; Fei Ge (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

Effects of table based air curtains on respiratory aerosol exposure risk mitigation at face-to-face meeting setups - Yinshuai Feng; Yu Feng; Yifan Fan; Jian Ge (Journal of Hazardous Materials, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Ecotoxicological evaluation and regeneration impairment of planarians by dibutyl phthalate - Fan Wu; Zhihong Kong; Peng Ge; Dandan Sun; Dezeng Liu; Zimei Dong; Guangwen Chen (Environmental Research, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

Flow patterns and heat transfer of an idealized square city in non-uniform heat flux and different background wind conditions - Xiaoliang Teng; Yan Zhang; Yifan Fan; Jian Ge (Building and Environment, 2024)

Volatility and chemical composition of secondary organic aerosol derived from acenaphthylene and acenaphthene under various oxidant conditions - Wang Xiang; Weigang Wang; Chunyan Hou; CiCi Fan; Ting Lei; Junling Li; Maofa Ge (Atmospheric Environment, 2024)

Similar experimental study on diffusion and distribution of diesel exhaust in confined space of a coal mine - Zhiyan Liu; Xi Chen; Chaonan Fan; Shaocheng Ge; Cunbao Deng; Weichao Li (Environmental Geochemistry and Health, 2024)

Viral communities locked in high elevation permafrost up to 100 m in depth on the Tibetan Plateau - Qian Wen; Xiufeng Yin; Abulimiti Moming; Guangyue Liu; Boyong Jiang; Jun Wang; Zhaojun Fan; Wasim Sajjad; Yingying Ge; Shichang Kang; Shu Shen; Fei Deng (Science of The Total Environment, 2024)

Hierarchical Nash equilibrium seeking for optimal fault-tolerant formation control of networked MSVs in aggregative games - Yi-Fan Li; Ming-Feng Ge; Qian Chen; Teng-Fei Ding; Zhi-Wei Liu (Ocean Engineering, 2024)

Experiment evaluation and thermodynamic analysis of pulping modification on ordered conversion of bark in supercritical water - Hui Ge; Yong Huang; Zhaozheng Liu; Fan Liu; Yu-Nan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

Water effect on CO2 absorption mechanism and phase change behavior in [N1111][Gly]/EtOH anhydrous biphasic absorbent: In density functional theory and molecular dynamics view - Wufeng Jiang; Ge Gao; Xiaoyi Gao; Bin Xu; Fan Wu; Xiaoshan Li; Liqi Zhang; Cong Luo (Chemical Engineering Journal, 2024)

Mobile measurement background quantification methods for determining local traffic emissions and background source contributions to ammonia - Weiwei Pu; Yingruo Li; Di He; Fan Dong; Jin Wu; Xiangxue Liu; Yulu Qiu; Shuangshuang Ge; Zhiqiang Ma (Atmospheric Environment, 2024)

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

Impact of manufacturing processes on glycerolipid and polar lipid composition and ultrastructure in infant formula - Qian Liu; Yan Liu; Junying Zhao; Weicang Qiao; Juncai Hou; Yaling Wang; Minghui Zhang; Ge Jia; Yan Liu; Xiaofei Fan; Ziqi Li; Haidong Jia; et al. (Food Chemistry, 2024)

Recent advances in artificial intelligence boosting materials design for electrochemical energy storage - Xinxin Liu; Kexin Fan; Xinmeng Huang; Jiankai Ge; Yujie Liu; Haisu Kang (Chemical Engineering Journal, 2024)

Identification of important gene signatures in schizophrenia through feature fusion and genetic algorithm - Zhixiong Chen; Ruiquan Ge; Changmiao Wang; Ahmed Elazab; Xianjun Fu; Wenwen Min; Feiwei Qin; Gangyong Jia; Xiaopeng Fan (Mammalian Genome, 2024)

Significant contribution of carbonyls to atmospheric oxidation capacity (AOC) during the winter haze pollution over North China Plain - Xue Yang; Gen Zhang; Guang Pan; Guolan Fan; Houyong Zhang; Xuan Ge; Mingyue Du (Journal of Environmental Sciences, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Comparative study on the foam and air-water interface properties of ethanol-soluble and non-ethanol components in wheat aqueous phase protein - Muyuan Zhao; Liya Liu; Ge Wang; Muhammad Awais; Litao Tong; Bei Fan; Aijun Hu; Fengzhong Wang (Food Hydrocolloids, 2024)

METH exposure alters sperm DNA methylation in F0 mice and mPFC transcriptome in male F1 mice - Zhaosu Li; Dekang Liu; Guanxiong Wang; Yanyan Zheng; Liying Chen; Zhen Cheng; Zijing Zhang; Qinglong Cai; Feifei Ge; Yu Fan; Xiaowei Guan (Psychopharmacology, 2024)

Evaluating infection risks in buses based on passengers' dynamic temporal and typical spatial scenarios: A case study of COVID-19 - Yinshuai Feng; Xiaoyu Luo; Jianjian Wei; Yifan Fan; Jian Ge (Science of The Total Environment, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Response of late Holocene vegetation to abrupt climatic events on the northwestern coast of the Bay of Bohai, China - Rongrong Wang; Yuecong Li; Shengrui Zhang; Qinghai Xu; Yawen Ge; Bing Li; Baoshuo Fan; Zhen Zhang; Cange Li; Ying Wang; Hanfei You; Yihang Cao; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Global wild rice germplasm resources conservation alliance: World Wild-Rice Wiring - Xiaoming Zheng; Disna Ratnasekera; Jiayu Fan; Robert J. Henry; Beng-Kah Song; Kenneth M. Olsen; Bal Krishna Joshi; Maria Celeste N. Banaticla-Hilario; Tonapha Pusadee; Adane Getachew Melaku; Yêyinou Laura Estelle Loko; Koukham Vilayheuang; et al. (Molecular Plant, 2024)

Secondary organic aerosols from oxidation of 1-methylnaphthalene: Yield, composition, and volatility - Wang Xiang; Weigang Wang; Chunyan Hou; CiCi Fan; Ting Lei; Junling Li; Maofa Ge (Science of The Total Environment, 2024)

The interaction between CmPIF8 and CmACO1 under postharvest red light treatment might affect fruit ripening and sucrose accumulation in oriental melon fruit - Jingyue Guan; Xue Liang; Ge Gao; Fan Yang; Hongyan Qi (Postharvest Biology and Technology, 2024)

Effects of microplastics on photosynthesized C allocation in a rice-soil system and its utilization by soil microbial groups - Zhi’e Hu; Mouliang Xiao; Jialing Wu; Yaoyao Tong; Jianhong Ji; Qing Huang; Fan Ding; Jina Ding; Zhenke Zhu; Jianping Chen; Tida Ge (Journal of Hazardous Materials, 2024)

Alkaline pulping catalyzed ordered conversion of bark in supercritical water - Hui Ge; Yong Huang; Zhaozheng Liu; Fan Liu; Yu-nan Chen; Liejin Guo (Journal of Cleaner Production, 2024)

Multiphase flow and reactor optimization of a 1MWth pilot-scale circulating fluidized bed for coal staged conversion - Yuxin Ge; Jiahui Yu; Junjie Lin; Shuai Wang; Kun Luo; Qinhui Wang; Jianren Fan (Chemical Engineering Journal, 2024)

Tumoral/exosomal PD-L1 silencing reinforces mild photothermal therapy by relieving systemic and local immunosuppression - Huan Ye; Jing Yan; Chenglong Ge; Fan Wu; Junliang Zhu; Mengyuan Yin; Lucheng Xie; Zhuchao Zhou; Lichen Yin (Chemical Engineering Journal, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Potential Role of Bmal1 in Lipopolysaccharide-Induced Depression-Like Behavior and its Associated "Inflammatory Storm" - Dan-Dan Xu; Zhi-Qi Hou; Ya-Yun Xu; Jun Liang; Ye-Jun Gao; Chen Zhang; Fan Guo; Dan-Dan Huang; Jin-Fang Ge; Qing-Rong Xia (Journal of Neuroimmune Pharmacology, 2024)

Measurement of perfluoroalkyl substances in drinking water sources by DGT sampler with a novel fluorinated graphite binding gel - Fan Dong; Fan Ge; Xinting Zhao; Daming Sun; Suyu Ren; Yan Wang; Feng Tan (Science of The Total Environment, 2024)

Mechanical property test and numerical analysis of a novel precast shear wall - Miao Xinwei; Huang Wei; Fan Zhenhui; Zhang Jiarui; Ge Pei (Engineering Structures, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Contribution of recycled oceanic crust to the extremely light molybdenum isotopic compositions of mid-ocean ridge basalts from the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Jie Li; Fan Yang; Zhen-Min Ge (Chemical Geology, 2024)

Contrasting effects of maize straw and its biochar on aggregation and soil organic matter stabilization - Dechang Ji; Liwei Ge; Lukas Van Zwieten; Tingting An; Shuangyi Li; Yakov Kuzyakov; Fan Ding; Jingkuan Wang (Plant and Soil, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Direct observations of nanoscale brushite dissolution by the concentration-dependent adsorption of phosphate or phytate - Xinfei Ge; Yuke Fan; Hang Zhai; Jialin Chi; Christine V. Putnis; Lijun Wang; Wenjun Zhang (Water Research, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Climate and sea-level fluctuations on the western coast of Bohai Bay during the 4.2 ka event: Multi-proxy evidence from the Nandagang area of Cangzhou, China - Hanfei You; Yuecong Li; Shengrui Zhang; Yawen Ge; Zhen Zhang; Wensheng Zhang; Ying Wang; Baoshuo Fan; Rongrong Wang; Yihang Cao; Cange Li (Quaternary Science Reviews, 2024)

Indoor air quality of urban public transportation stations in China: Based on air quality evaluation indexes - Lin Fan; Xu Han; Li Li; Hang Liu; Tanxi Ge; Xinqi Wang; Qin Wang; Hang Du; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2024)

Kinetic and mechanism of the reaction between Cl and several mono-methyl branched alkanes - Yan Chen; Weigang Wang; Junling Li; Li Zhou; Bo Shi; Cici Fan; Ke Wang; Hao Zhang; Hong Li; Maofa Ge (Journal of Environmental Sciences, 2024)

Reaction behaviors in pulverized coal MILD-oxy combustion affected by physical and chemical effects of diluents - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2024)

Metasomatized mantle source of nascent oceanic crust in the Guaymas Basin, Gulf of California - Zhen-Min Ge; Xiao-Long Huang; Wei Xie; Tobias W. Höfig; Fan Yang; Yang Yu; S. Khogenkumar Singh (Chemical Geology, 2024)

Tracking photosynthetic phenology using spectral indices at the leaf and canopy scales in temperate evergreen and deciduous trees - Jiaqi Guo; Xiaohong Liu; Wensen Ge; Liangju Zhao; Wenjie Fan; Xinyu Zhang; Qiangqiang Lu; Xiaoyu Xing; Zihan Zhou (Agricultural and Forest Meteorology, 2024)

RETRACTED: High-efficiency and low-carbon inactivation of UV resistant bacteria in reclaimed water by flow-through electrode system (FES) - Yi-Ge Sun; Hao-Bin Wang; Yin-Hu Wu; Ke-Fan Cao; Zhuo Chen; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Science of The Total Environment, 2023)

Prime editing: current advances and therapeutic opportunities in human diseases - Yidian Fu; Xiaoyu He; Xin D. Gao; Fang Li; Shengfang Ge; Zhi Yang; Xianqun Fan (Science Bulletin, 2023)

Nightmare or delight: Taxonomic circumscription meets reticulate evolution in the phylogenomic era - Ze-Tao Jin; Richard G.J. Hodel; Dai-Kun Ma; Hui Wang; Guang-Ning Liu; Chen Ren; Bin-Jie Ge; Qiang Fan; Shui-Hu Jin; Chao Xu; Jun Wu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2023)

A sustainable strategy to transform cotton waste into renewable cellulose fiber self-reinforcing composite paper - Chan Wang; Jinhui Su; Taoyuan Liu; Shengbo Ge; Rock Keey Liew; Hui Zhang; Mu Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Wei Fan (Journal of Cleaner Production, 2023)

Design and fabrication of Zn@ZnO@Ag chip for Raman scattering analysis of norfloxacin in liquid milk, fish and animal feeds - Hanqiang Zhang; Xuejing Fan; Yangyue Ding; Lunzhao Yi; Kun Ge; Ying Gu (Food Chemistry, 2023)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Facile spinning of tough and conductive eutectogel fibers via Li+-induced dense hydrogen-bond networks - Lingtao Fang; Chi Zhang; Wenjiao Ge; Mingming Rong; Fan Chen; Zijian Chen; Xiaohui Wang; Zijian Zheng; Qiyao Huang (Chemical Engineering Journal, 2023)

Synthesis and applications of carbon quantum dots derived from biomass waste: a review - Jiayu Wu; Tianyue Chen; Shengbo Ge; Wei Fan; Hui Wang; Zhongfeng Zhang; Eric Lichtfouse; Thuan Van Tran; Rock Keey Liew; Mashallah Rezakazemi; Runzhou Huang (Environmental Chemistry Letters, 2023)

Urban surface classification using semi-supervised domain adaptive deep learning models and its application in urban environment studies - Xiaotian Ding; Yifan Fan; Yuguo Li; Jian Ge (Environmental Science and Pollution Research, 2023)

The effect of functional ionic liquids on the microstructure and wettability of coals with different metamorphic degrees - Xi Chen; Jiayan Lv; Chaonan Fan; Shaocheng Ge; Cunbao Deng; Jiahui Gao (Fuel, 2023)

Potential role of cell wall pectin polysaccharides, water state, and cellular structure on twice “increase–decrease” texture changes during kohlrabi pickling process - Zhixuan Yang; Hekai Fan; Ruoxuan Li; Bowen Li; Jiangtao Fan; Jinjiang Ge; Xiaoyun Xu; Siyi Pan; Fengxia Liu (Food Research International, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

A new attempt to control volatile organic compounds (VOCs) pollution - Modification technology of biomass for adsorption of VOCs gas - Guiyang Zheng; Kexin Wei; Xuelian Kang; Wei Fan; Nyuk Ling Ma; Meenakshi Verma; Hui Suan Ng; Shengbo Ge (Environmental Pollution, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

An intelligent identification method of interlayers in deep clastic rock – An example of Donghe Sandstone in Hade Oilfield, Tarim Basin - Jier Zhao; Yiren Fan; Xinmin Ge; Wei Wang; Zhengjun Zhu; Min Wang; Dongyue Zhao (Marine and Petroleum Geology, 2023)

New insights into the structure-activity relationship for CO2 capture by tertiary amines from the experimental and quantum chemical calculation perspectives - Ge Gao; Bin Xu; Xiaoyi Gao; Wufeng Jiang; Zhenghong Zhao; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2023)

Two sesquiterpene lactones, arnicolide B and arnicolide C, isolated from Centipeda minima , exert anti-inflammatory effects in LPS stimulated RAW 264.7 macrophages via inactivation of the MAPK pathway - Ge Wang; Hongfang Liu; Qingran Zhang; Xiaofeng Mou; Yan Zhao; Huaying Fan; Hui Xu; Daquan Chen; Feng Qiu; Feng Zhao (Natural Product Research, 2023)

Effects of dietary α-ketoglutarate on the growth performance, digestive enzymes, tor signaling pathway and intestinal microbiota of juvenile mirror carp (Cyprinus carpio) fed low phosphorus diets - Liansheng Wang; Ze Fan; Di Wu; Jinnan Li; Qiyou Xu; Linghong Miao; Xianping Ge; Dingcheng Cao; Xianhu Zheng (Aquaculture, 2023)

Modeling and optimization of synergistic ozone-ultraviolet-chlorine process for reclaimed water disinfection: From laboratory tests to software simulation - Ke-Fan Cao; Zhuo Chen; Yi-Ge Sun; Bang-Hao Huang; Qi Shi; Yu Mao; Yin-Hu Wu; Yun Lu; Hong-Ying Hu (Water Research, 2023)

Bavachin induces liver injury and cell apoptosis by targeting Wnt/β-catenin/DRP1 signaling pathway mediated mitochondrial dysfunction - Ying Yang; Wei Zhou; Yihao Wang; Yunxuan Ge; Zheng Fan; Qingquan Liu; Yue Gao (Toxicology Letters, 2023)

Middle to late Holocene environmental evolution and sea level change on the west coast of Bohai Bay - Siyu Wang; Yuecong Li; Baoshuo Fan; Yihang Cao; Hanfei You; Rongrong Wang; Yawen Ge; Shuoqiang Da; Zijing She; Zhen Zhang; Shengrui Zhang; Cange Li (Quaternary International, 2023)

Morphological and architectural evolution of submarine channels: An example from the world's largest submarine fan in the Bay of Bengal - Dongwei Li; Chenglin Gong; Guozhang Fan; Ronald J. Steel; Daoyao Ge; Dali Shao; Liangbo Ding (Marine and Petroleum Geology, 2023)

Momordica charantia saponins administration in low-protein-high-carbohydrate diet improves growth, blood biochemical, intestinal health and microflora composition of juvenile common carp (Cyprinus carpio) - Ze Fan; Liansheng Wang; Jinnan Li; Di Wu; Chenhui Li; Xianhu Zheng; Haitao Zhang; Linghong Miao; Xianping Ge (Fish & Shellfish Immunology, 2023)

Arsenic induced autophagy-dependent apoptosis in hippocampal neurons via AMPK/mTOR signaling pathway - Yao Chen; Xudan Liu; Qianhui Zhang; Huanhuan Wang; Ruo Zhang; Yanhong Ge; Huning Liang; Wanying Li; Juanjun Fan; Huimin Liu; Zhengyang Lv; Wenting Dou; et al. (Food and Chemical Toxicology, 2023)

RETRACTED: Multi-scale experimental investigation on the fluidization of Geldart B 13X zeolite particles: A comprehensive dataset for CFD validation - Mingming Ge; Hang Zhou; Avinash Vaidheeswaran; William Rogers; Dixia Fan; Cheng Li (Chemical Engineering Journal, 2023)

3D printing MOF nanozyme hydrogel with dual enzymatic activities and visualized glucose monitoring for diabetic wound healing - Ziyan Chen; Shen Song; Huajing Zeng; Zhenlin Ge; Bin Liu; Zengjie Fan (Chemical Engineering Journal, 2023)

A waste textiles-based multilayer composite fabric with superior electromagnetic shielding, infrared stealth and flame retardance for military applications - Yuhan Zhang; Guodong Shen; Su Shiung Lam; Sabah Ansar; Sang-Chul Jung; Shengbo Ge; Lin Hou; Zhengke Fan; Feng Wang; Wei Fan (Chemical Engineering Journal, 2023)

3D printing for bone repair: Coupling infection therapy and defect regeneration - Jiatian Chen; Huaijuan Zhou; Yingwei Fan; Ge Gao; Yulong Ying; Jinhua Li (Chemical Engineering Journal, 2023)

Distribution of microplastics in soil aggregates after film mulching - Yuhuai Liu; Yingying Zhong; Can Hu; Mouliang Xiao; Fan Ding; Yongxiang Yu; Huaiying Yao; Zhenke Zhu; Jianping Chen; Tida Ge; Jina Ding (Soil Ecology Letters, 2023)

Tuning functional ionic deep eutectic solvents as green sorbents and catalysts for highly efficient capture and transformation of CO2 to quinazoline-2,4(1H,3H)-dione and its derivatives - Guokai Cui; Yisha Xu; Daqing Hu; Ying Zhou; Chunliang Ge; Huayan Liu; Wenyang Fan; Zekai Zhang; Biao Chen; Quanli Ke; Yaoji Chen; Bing Zhou; et al. (Chemical Engineering Journal, 2023)

Multi-scale risk assessment and mitigations comparison for COVID-19 in urban public transport: A combined field measurement and modeling approach - Yinshuai Feng; Yan Zhang; Xiaotian Ding; Yifan Fan; Jian Ge (Building and Environment, 2023)

Reclamation effects of distinct volumes and concentrations of CaCl2-amended brackish ice in different saline-sodic soils - Lu Zhang; An-Hui Ge; Tibor Tóth; Fan Yang; Zhichun Wang; Fenghua An (Journal of Environmental Management, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

The combined effect of seawater salinity and duration on the survival and growth of eelgrass Zostera marina - Yan-Hao Zhang; Jian-Du Li; Wen-Jie Yan; Fan-Shu Luo; Li Wang; Li-Ming Zuo; Jun-Ge Xu; Wen-Tao Li; Pei-Dong Zhang (Aquatic Botany, 2023)

Association Between IL10 Polymorphisms and the Susceptibility to Sepsis: A Meta-Analysis - Ning Zhang; Siting Wang; Yipan Fan; Changding Sheng; Weixing Ge (Biochemical Genetics, 2023)

Elevated CO2 altered the nano-ZnO-induced influence on bacterial and fungal composition in tomato (Solanum lycopersicum L.) rhizosphere soils - Hehua Wang; Haoxin Fan; Yaying Li; Chaorong Ge; Huaiying Yao (Environmental Science and Pollution Research, 2023)

Urban heat dome flow deflected by the Coriolis force - Yan Zhang; Xiaoxue Wang; Yifan Fan; Yongling Zhao; Jan Carmeliet; Jian Ge (Urban Climate, 2023)

A comparative study of the accumulation and detoxification of copper and zinc in Chlamydomonas reinhardtii: The role of extracellular polymeric substances - Chonghua Li; Peihuan Li; Hongxuan Fu; Jiale Chen; Menglei Ye; Suhua Zhai; Fan Hu; Chunhua Zhang; Ying Ge; Claude Fortin (Science of The Total Environment, 2023)

Molecular insights into effects of PBAT microplastics on latosol microbial diversity and DOM chemodiversity - Yuqin Liu; Wen Zhang; Miao Chen; Xiongwei Zhao; Huiran Liu; Meihong Ge; Ning Li; Ziyu Ning; Wenlong Gao; Changhua Fan; Qinfen Li (Journal of Hazardous Materials, 2023)

Combustion behaviors of pulverized coal MILD-oxy combustion under different steam injection parameters - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Xiaoshan Li; Fan Wu; Cong Luo; Liqi Zhang (Fuel, 2023)

Tuning ionic liquid-based functional deep eutectic solvents and other functional mixtures for CO2 capture - Yisha Xu; Ruina Zhang; Ying Zhou; Daqing Hu; Chunliang Ge; Wenyang Fan; Biao Chen; Yaoji Chen; Wei Zhang; Huayan Liu; Guokai Cui; Hanfeng Lu (Chemical Engineering Journal, 2023)

Photolysis of chlorite by solar light: An overlooked mitigation pathway for chlorite and micropollutants - Tao Yang; Mengyang Zhu; Linqian An; Ge Zeng; Chengqian Fan; Juan Li; Jin Jiang; Jun Ma (Water Research, 2023)

Maize straw mulching with no-tillage increases fertile spike and grain yield of dryland wheat by regulating root-soil interaction and nitrogen nutrition - Hongkun Yang; Jingang Li; Ge Wu; Xiulan Huang; Gaoqiong Fan (Soil and Tillage Research, 2023)

Sulfur transformation mechanism during supercritical water gasification of black liquor - Libo Lu; Wenwen Wei; Fan Liu; Zhiwei Ge; Hui Jin; Yunan Chen; Liejin Guo (Fuel, 2023)

Effect of active composite ionic liquids treatment on chemical structure and wettability of coal - Xi Chen; Jiahui Gao; Cunbao Deng; Shaocheng Ge; Chaonan Fan; Wei Zhang (Fuel, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Machine learning-assisted mapping of city-scale air temperature: Using sparse meteorological data for urban climate modeling and adaptation - Xiaotian Ding; Yongling Zhao; Yifan Fan; Yuguo Li; Jian Ge (Building and Environment, 2023)

Characteristics, chemical transformation and source apportionment of volatile organic compounds (VOCs) during wintertime at a suburban site in a provincial capital city, east China - BaoLin Wang; ZhenGuo Liu; ZiAng Li; YuChun Sun; Chen Wang; ChuanYong Zhu; Lei Sun; Na Yang; Ge Bai; GuoLan Fan; XiaoYan Sun; ZhiYong Xia; et al. (Atmospheric Environment, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Influence mechanism of ammonia mixing on NO formation characteristics of pulverized coal combustion and N oxidation in ammonia-N/coal-N - Ping Chen; Changhao Hua; Boyu Jiang; Mingyan Gu; Zhenling Ge; Meng Zhang; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Enhanced Lipid Productivity in Low-Starch Mutant of Monoraphidium sp. for Biodiesel Production - Yimeng Lin; Yunye Zhang; Yang Fan; Chang Li; Hongzhi Ling; Wenxiang Ping; Jingping Ge (BioEnergy Research, 2023)

Full-scale experimental and numerical study of smoke spread characteristics in a long-closed channel with one lateral opening - Weixin Tong; Fanliang Ge; Long Ding; Jie Ji; Yuanlong Zhou; Yang Zhou; Fan Zhou (Tunnelling and Underground Space Technology, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Mn-induced strengthening hybridization effect of Co–O bond for stable oxygen evolution in acidic media - Ruo-Yao Fan; Hui-Ying Zhao; Yi-Nuo Zhen; Feng-Ge Wang; Han Hu; Yong-Ming Chai; Bin Dong (Fuel, 2023)

Multiple-objective optimization of Jet Controlled Compression Ignition (JCCI) mode with dual-direct injection in a high-speed light-duty engine - Bo Li; Jian Wang; Heng Zhang; Liyun Fan; Xianyin Leng; Wuqiang Long; Ge Xiao (Fuel, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

A numerical rotating water tank can reproduce the Coriolis effect on the urban heat dome flow - Yifan Fan; Yan Zhang; Shaopeng Wang; Xiaoxue Wang; Jiang Lu; Jian Ge (Building and Environment, 2023)

Inhibition of cGAS ameliorates acute lung injury triggered by zinc oxide nanoparticles - Ziqi Jiang; Yu Jiang; Jingchuan Fan; Jun Zhang; Ge Xu; Yinzhen Fan; Liyu Zhang; Xia Qin; Xuejun Jiang; Lejiao Mao; Gang Liu; Chengzhi Chen; et al. (Toxicology Letters, 2023)

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

Blockchain-like E α analysis strategy for two distinct “White-box” modeling methodologies to simulate the incineration of oily sludge - Yuanfeng Qi; Wei Wang; Xiao Quan; Chenxi Fan; Baoxin Ge; Chang Xu; Mingyang Cui; Qinyan Yue; Baoyu Gao; Yue Gao; Kai He (Journal of Cleaner Production, 2023)

Fuel-NO formation mechanism in MILD-oxy combustion of CH4/NH3 fuel blend - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2023)

Identification of high iron–chelating peptides with unusual antioxidant effect from sea cucumbers and the possible binding mode - Chaozhong Fan; Xiaofan Ge; Junyu Hao; Tao Wu; Rui Liu; Wenjie Sui; Jieting Geng; Min Zhang (Food Chemistry, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Heat and moisture transfer in wall-to-floor thermal bridges and its influence on thermal performance - Yucong Xue; Yifan Fan; Shuqin Chen; Zitao Wang; Weijun Gao; Zhijian Sun; Jian Ge (Energy and Buildings, 2023)

Helical configuration channels boost performance in anion exchange membranes - Yang Zhang; Fan Zhang; Yiwen Chen; Lixuan Sun; Chengpeng Wei; Huaqing Zhang; Hongjun Zhang; Bangjiao Ye; Liang Wu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2023)

The direct modification of metal Cu interface for high-performing solid-state anode via KCu7S4/Cu7S4 interconversion mechanism - Tianyi Gao; Tianyu xiao; Yunshuang Ge; Shuai Zhang; Zimeng Wang; Zhongyu Wang; Zhipeng Ma; Wenfeng Guo; Yuqian Fan (Chemical Engineering Journal, 2023)

Hydrogeological Control on Coalbed Methane Geochemistry in CO2/N2-Enriched Secondary Microbial Gas Areas: A Case Study in the Eastern Section of the Southern Junggar Basin, NW China - Baoxin Zhang; Ze Deng; Xuehai Fu; Yibing Wang; Longjiang Fan; Junqiang Kang; Zhenzhi Wang; Yanyan Ge (Natural Resources Research, 2022)

Recycling of bast textile wastes into high value-added products: a review - Xue Yang; Wei Fan; Hui Wang; Yang Shi; Shujuan Wang; Rock Keey Liew; Shengbo Ge (Environmental Chemistry Letters, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Visualization and quantification of carbon “rusty sink” by rice root iron plaque: Mechanisms, functions, and global implications - Liang Wei; Zhenke Zhu; Bahar S. Razavi; Mouliang Xiao; Maxim Dorodnikov; Lichao Fan; Hongzhao Yuan; Andrey Yurtaev; Yu Luo; Weiguo Cheng; Yakov Kuzyakov; Jinshui Wu; et al. (Global Change Biology, 2022)
Paddies contain 78% higher organic carbon (C) stocks than adjacent upland soils, and iron (Fe) plaque formation on rice roots is one of the mechanisms that traps C. The process sequence, extent and global relevance of this C stabilization mechanism under oxic/anoxic conditions remains unclear. We quantified and localized the contribution of Fe plaque to organic matter stabilization in a microoxic area (rice rhizosphere) and evaluated roles of this C trap for global C sequestration in paddy soils. Visualization and localization of pH by imaging with planar optodes, enzyme activities by zymography, and root exudation by 14 C imaging, as well as upscale modeling enabled linkage of three groups of rhizosphere processes that are responsible for C stabilization from the micro‐ (root) to the macro‐ (ecosystem) levels. The 14 C activity in soil (reflecting stabilization of rhizodeposits) with Fe 2+ addition was 1.4–1.5 times higher than that in the control and phosphate addition soils. Perfect co‐localization of the hotspots of β‐glucosidase activity (by zymography) with root exudation ( 14 C) showed that labile C and high enzyme activities were localized within Fe plaques. Fe 2+ addition to soil and its microbial oxidation to Fe 3+ by radial oxygen release from rice roots increased Fe plaque (Fe 3+ ) formation by 1.7–2.5 times. The C amounts trapped by Fe plaque increased by 1.1 times after Fe 2+ addition. Therefore, Fe plaque formed from amorphous and complex Fe (oxyhydr)oxides on the root surface act as a “rusty sink” for organic matter. Considering the area of coverage of paddy soils globally, upscaling by model revealed the radial oxygen loss from roots and bacterial Fe oxidation may trap up to 130 Mg C in Fe plaques per rice season. This represents an important annual surplus of new and stable C to the existing C pool under long‐term rice cropping.

Temperature has a strong impact on the abundance and community structure of comammox Nitrospira in an Ultisol - Mengmeng Feng; Zi-Yang He; Jianbo Fan; An-Hui Ge; Shengsheng Jin; Yongxin Lin; Ji-Zheng He (Journal of Soils and Sediments, 2022)

Stable carbon isotopes of dissolved inorganic carbon in the Western North Pacific Ocean: Proxy for water mixing and dynamics - Tiantian Ge; Chunle Luo; Peng Ren; Hongmei Zhang; Di Fan; Hongtao Chen; Zhaohui Chen; Jing Zhang; Xuchen Wang (Frontiers in Marine Science, 2022)
The uptake of atmospheric CO 2 and the cycle of dissolved inorganic carbon (DIC) in the ocean are the major mechanisms and pathways controlling global climate change and carbon cycling. The stable carbon isotope (δ 13 C) of DIC, therefore, provides an important tracer for processes such as air-sea exchange, photosynthesis, and water dynamics in the ocean. Here, we present new δ 13 C-DIC data on water samples collected from a north-south transect (13°N–40°N, 150°E) in the western North Pacific (NP) Ocean in November 2019 and compare the results with those previously reported for similar transects (149.3°E) during WOCE and CLIVAR projects over the past three decades. The values of δ 13 C-DIC, ranging from -0.83‰ to 0.86‰, were higher in the surface waters and decreased with depth. The high δ 13 C-DIC values in the surface waters were influenced primarily by isotopic fractionation during air-sea exchange and photosynthesis. With depth, the movement of different water masses and mixing, as well as bathypelagic respiration in the dark water of the ocean, all play important roles in influencing the distribution and isotopic signatures of δ 13 C-DIC in the western NP Ocean. The δ 13 C-DIC values of the 0–200 m water layer varied from -0.17‰ to 0.86‰, with lower values at high latitudes, affected by the low δ 13 C-DIC values carried by the Oyashio Current to the Kuroshio Extension (KE) region. A downward trend was present in the δ 13 C-DIC signature from north to south in the North Pacific Intermediate Water (NPIW) and Pacific Deep Water (PDW) in the western NP, which reflected the remineralization of organic matter with a horizontal transport of NPIW and PDW. We found a strong 13 C Suess Effect in the upper 2,000 m in the western NP Ocean, and δ 13 C-DIC at the surface (<50 m) has decreased by 0.60‰-0.85‰ since 1993. The mean δ 13 C-DIC change in the surface ocean was estimated at 0.28‰ per decade between 1993 and 2019. The air-sea exchange and water mixing in the study area may have accelerated the absorption of anthropogenic CO 2 in recent years, which likely caused a slightly faster rate of decrease in the δ 13 C-DIC from 2005–2019 than that observed from 1993–2005.

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Household solid fuel use with diabetes and fasting blood glucose levels among middle-aged and older adults in China - Yuxiong Chen; Siqin Feng; Zhen’ge Chang; Yakun Zhao; Jia Fu; Yijie Liu; Siqi Tang; Yitao Han; Yanbo Liu; Yuanxun Zhang; Shuyang Zhang; Zhongjie Fan (Environmental Science and Pollution Research, 2022)

Real wine or not? Protecting wine with traceability and authenticity for consumers: chemical and technical basis, technique applications, challenge, and perspectives - Xiangyu Sun; Fan Zhang; Gastón Gutiérrez-Gamboa; Qian Ge; Pingkang Xu; Qianwen Zhang; Yulin Fang; Tingting Ma (Critical Reviews in Food Science and Nutrition, 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

PRMT6/LMNA/CXCL12 signaling pathway regulated the osteo/odontogenic differentiation ability in dental stem cells isolated from apical papilla - Ning Wang; Miao Li; Yangyang Cao; Haoqing Yang; Le Li; Lihua Ge; Zhipeng Fan; Chen Zhang; Luyuan Jin (Cell and Tissue Research, 2022)

Genome characterization and comparative analysis among three swimming crab species - Ming Liu; Shanshan Ge; Shivish Bhandari; Chunlei Fan; Yu Jiao; Chunlei Gai; Youhong Wang; Hongjun Liu (Frontiers in Marine Science, 2022)
In this study we sequenced the genomes of three economically important swimming crabs Portunus trituberculatus, Charybdis japonica , and Callinectes sapidus using the next-generation sequencing approach and made a basic assembly. The genomes of the three species are characterized with high heterozygosity (>1.2%) and high repeat content (>50%). Genome comparative analysis revealed 40 long conserved fragments (>5,000 bp) among the three species, most of them are involved in cardiac-related biological process. Relative higher genome similarity was found between P. trituberculatus and C. japonica that are belong to different subfamilies, compared to that between P. trituberculatus and C. sapidus which are from the same subfamily. It is inconsistent with their phylogenetic evolutionary trees inferred from previous mitochondrial DNA coding fragments and a conserved ANK2 protein fragment from this study. We speculated that the high genome similarity between P. trituberculatus and C. japonica might be attributed to their same inhabit range in which the genome is subject to the same environment selection, and the inconsistence between genome similarity and phylogenetic relationship is caused by the different evolutionary rates of coding DNA and non-coding DNA under environment selection.

Development of a quantitative risk assessment method for a biomass gasification unit by combining DEMATEL-ISM and CM-TOPSIS - Jishuo Li; Kaili Xu; Ji Ge; Bingjie Fan (Stochastic Environmental Research and Risk Assessment, 2022)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Nanosecond pulsed electric fields prime mesenchymal stem cells to peptide ghrelin and enhance chondrogenesis and osteochondral defect repair in vivo - Kejia Li; Litong Fan; Jianjing Lin; Boon Chin Heng; Zhantao Deng; Qiujian Zheng; Jue Zhang; Yangzi Jiang; Zigang Ge (Science China Life Sciences, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Evaluation of Allicin Against Alveolar Echinococcosis In Vitro and in a Mouse Model - Chuanchuan Liu; Haining Fan; Lu Guan; Lan Ma; Ri-li Ge (Acta Parasitologica, 2022)
Purpose At present, the chemotherapy for alveolar echinococcosis (AE) is mainly based on albendazole (ABZ). However, more than 20% of patients fail chemotherapy. Therefore, new and more effective treatments are urgently needed. Allicin has been reported to have antibacterial and antiparasitic effects. The objectives of the present study were to investigate the in vivo and in vitro efficacy of allicin against Echinococcus multilocularis ( E. multilocularis ). Methods The effects of allicin on protoscolex survival and structural changes were evaluated in vitro . The 4-week-old BALB/c male mice used for in vivo modelling underwent inoculation of E. multilocularis protoscoleces by intraperitoneal injection, followed by intragastric administration of allicin for 6 weeks. Then, the effects of allicin on lymphocyte subsets, metacestode growth and host tissue matrix metalloproteinase 2 (MMP2)/MMP9 expression around metacestodes in mice were evaluated. The toxicity of allicin was further evaluated in vivo and in vitro . Results Att 40 μg/mL, allicin showed a killing effect on protoscoleces in vitro and treatment resulted in the destruction of protoscolex structure. Molecular docking showed that allicin could form hydrogen bonds with E. multilocularis cysteine enzymes. After 6 weeks of in vivo allicin treatment, the spleen index of mice was increased and the weight of metacestodes was reduced. Allicin increased the proportion of CD4 + T cells and decreased the proportion of CD8 + T cells in the peripheral blood and spleen. Pathological analysis of the metacestodes showed structural disruption of the germinal and laminated layers after allicin treatment. In addition, allicin inhibited the expression of MMP2 and MMP9 in metacestode-surrounding host tissues. At 160 μg/mL, allicin had no significant toxicity to normal hepatocytes but could inhibit hepatoma cell proliferation. At 30 mg/kg, allicin had no significant hepatorenal toxicity in vivo . Conclusion These results suggest that allicin exerts anti- E. multilocularis effects in vitro and in vivo and can enhance immune function in mice, with the potential to be developed as a lead compound against echinococcosis.

Identification and analysis of oil candidate genes reveals the molecular basis of cottonseed oil accumulation in Gossypium hirsutum L. - Zhibin Zhang; Juwu Gong; Zhen Zhang; Wankui Gong; Junwen Li; Yuzhen Shi; Aiying Liu; Qun Ge; Jingtao Pan; Senmiao Fan; Xiaoying Deng; Shaoqi Li; et al. (Theoretical and Applied Genetics, 2022)

Bacteria-based nanosystems for enhanced antitumor therapy - Yu Han; Miao Fan; Dandan Han; Kun Ge; Jin Chang; Jinchao Zhang (Science China Life Sciences, 2022)

Individual willingness to prepare for disasters in a geological hazard risk area: an empirical study based on the protection motivation theory - Shi-yu Hu; Miao Yu; Ting Que; Gang Fan; Hui-ge Xing (Natural Hazards, 2022)

Prediction and validation of cross-protective candidate antigen of Hyalomma asiaticum cathepsin L between H. asiaticum and H. anatolicum - Ruiqi Song; Xuejie Zhai; Xinli Fan; Yongchang Li; Huercha; Ting Ge; Caishan Li; Min Li; Wenwen He; Huizhen Zheng; Lu Gan; Yang Zhang; et al. (Experimental and Applied Acarology, 2022)

Temperature sensitivity of anaerobic methane oxidation versus methanogenesis in paddy soil: Implications for the CH 4 balance under global warming - Lichao Fan; Michaela A. Dippold; Volker Thiel; Tida Ge; Jinshui Wu; Yakov Kuzyakov; Maxim Dorodnikov (Global Change Biology, 2022)
The global methane (CH 4 ) budget is based on a sensitive balance between methanogenesis and CH 4 oxidation (aerobic and anaerobic). The response of these processes to climate warming, however, is not quantified. This largely reflects our lack of knowledge about the temperature sensitivity ( Q 10 ) of the anaerobic oxidation of CH 4 (AOM)—a ubiquitous process in soils. Based on a 13 CH 4 labeling experiment, we determined the rate, Q 10 and activation energy of AOM and of methanogenesis in a paddy soil at three temperatures (5, 20, 35°C). The rates of AOM and of methanogenesis increased exponentially with temperature, whereby the AOM rate was significantly lower than methanogenesis. Both the activation energy and Q 10 of AOM dropped significantly from 5–20 to 20–35°C, indicating that AOM is a highly temperature‐dependent microbial process. Nonetheless, the Q 10 of AOM and of methanogenesis were similar at 5–35°C, implying a comparable temperature dependence of AOM and methanogenesis in paddy soil. The continuous increase of AOM Q 10 over the 28‐day experiment reflects the successive utilization of electron acceptors according to their thermodynamic efficiency. The basic constant for Q 10 of AOM was calculated to be 0.1 units for each 3.2 kJ mol −1 increase of activation energy. We estimate the AOM in paddy soils to consume 2.2~5.5 Tg CH 4 per year on a global scale. Considering these results in conjunction with literature data, the terrestrial AOM in total consumes ~30% of overall CH 4 production. Our data corroborate a similar Q 10 of AOM and methanogenesis. As the rate of AOM in paddy soils is lower than methanogenesis, however, it will not fully compensate for an increased methane production under climate warming.

Enhanced nitrogen and phosphorus removal by natural pyrite–based constructed wetland with intermittent aeration - Liya Li; Jingwei Feng; Liu Zhang; Hao Yin; Chunli Fan; Zechun Wang; Menglei Zhao; Chengchang Ge; Hao Song (Environmental Science and Pollution Research, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

Divergent responses in morphology and life history to an Asplanchna kairomone between attached and free-swimming Brachionus dorcas (Rotifera) - Shan Jiang; Yan Bai; Fan Sun; Le-Le Ge; Yi-Long Xi (Hydrobiologia, 2021)

Clinical significance of serum miR-487b in HBV-related hepatocellular carcinoma and its potential mechanism - Xiuping Li; Yuzhen Guo; Xiyan Wang; Anning Ge; Hui Wang; Kaiyun Fan; Changtong Guo (Infectious Diseases, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

A novel variant in GPAA1, encoding a GPI transamidase complex protein, causes inherited vascular anomalies with various phenotypes - Yongyun Li; Liu Yang; Jie Yang; Jiahao Shi; Peiwei Chai; Shengfang Ge; Yefei Wang; Xianqun Fan; Renbing Jia (Human Genetics, 2020)

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Effect of Chinese Rice Wine on the Endogenous Protease Activity, Myofibrillar Degradation, and Quality Characteristics in Topmouth Culter ( Culter alburnus ) - Fan Wang; Jia-Liang He; Tursunay Turgun; Da-E Ge; Nurgul Rahman; Jian-Zhong Zhou; Xiao-Li Liu (Journal of Aquatic Food Product Technology, 2020)

The effect of urbanization and spatial agglomeration on carbon emissions in urban agglomeration - Feng Wang; Wenna Fan; Juan Liu; Ge Wang; Wei Chai (Environmental Science and Pollution Research, 2020)

Conspicuous temperature extremes over Southeast Asia: seasonal variations under 1.5 °C and 2 °C global warming - Shoupeng Zhu; Fei Ge; Yi Fan; Ling Zhang; Frank Sielmann; Klaus Fraedrich; Xiefei Zhi (Climatic Change, 2020)

Impact of sea ice decline in the Arctic Ocean on the number of extreme low‐temperature days over China - Feifan Ge; Tao Yan; Lu Zhou; Yuelin Jiang; Wei Li; Yufen Fan; Yishu Wang; Kebiao Mao; Wenge Wu (International Journal of Climatology, 2020)
The variation in the number of extreme low‐temperature days (NELD) during winter over China is examined. The NELD mainly has a significant decreasing trend across China. The leading NELD empirical orthogonal function (EOF) mode also shows consistent change characteristics over China, and a Mann–Kendall (MK) test of its time coefficients indicates that the NELD abruptly changed in approximately 1980. The impact of sea ice concentrations in the Arctic Ocean on the NELD is investigated. Sea ice concentration declines in the Barents Sea and the sea east of Greenland have significant negative effects on the NELD. Sea surface temperatures in these regions are negatively correlated with the NELD. The study analyses the influence mechanism by researching the composite atmosphere variable anomalies between years with below‐normal NELD and those with above‐normal NELD.

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Smart calcium peroxide with self-sufficience for biomedicine - Shutao Gao; Miao Fan; Zhenhua Li; Kun Ge; Xing-Jie Liang; Jinchao Zhang (Science China Life Sciences, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Geographical distribution of the P-R interval reference value of Chinese healthy adults - Fan Yang; Miao Ge; Tianyu Li; Lu Chai (International Journal of Biometeorology, 2019)

Modified genetic algorithm with simulated annealing applied to optimal load dispatch of the Three Gorges Hydropower Plant in China - Yizi Shang; Qixiang Fan; Ling Shang; Zhiyu Sun; Ge Xiao (Hydrological Sciences Journal, 2019)

Quantitative trait locus mapping for plant height and branch number in an upland cotton recombinant inbred line with an SNP-based high-density genetic map - Zhen Zhang; Aiying Liu; Zhen Huang; Senmiao Fan; Xianyan Zou; Xiaoying Deng; Qun Ge; Juwu Gong; Junwen Li; Wankui Gong; Yuzhen Shi; Liqiang Fan; et al. (Euphytica, 2019)

Prevalence of shrimp microsporidian parasite Enterocytozoon hepatopenaei in Jiangsu Province, China - Hui Shen; Yi Qiao; Xihe Wan; Ge Jiang; Xianping Fan; Hui Li; Wenjun Shi; Libao Wang; Xiaoran Zhen (Aquaculture International, 2019)

Effects of UV-B radiation on the survival, egg hatchability and transcript expression of antioxidant enzymes in a high-temperature adapted strain of Neoseiulus barkeri - Chuan-Bei Tian; Ya-Ying Li; Xian Wang; Wen-Hui Fan; Ge Wang; Jing-Yu Liang; Zi-Ying Wang; Huai Liu (Experimental and Applied Acarology, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Efficient removal of ethidium bromide from aqueous solution by using DNA-loaded Fe3O4 nanoparticles - Zhiqiang Ge; Tingting Sun; Jinfeng Xing; Xuejiao Fan (Environmental Science and Pollution Research, 2019)

Immobilized β-lactamase on Fe3O4 magnetic nanoparticles for degradation of β-lactam antibiotics in wastewater - X. J. Gao; X. J. Fan; X. P. Chen; Z. Q. Ge (International Journal of Environmental Science and Technology, 2018)

Hydrothermal synthesis of a magnetic adsorbent from wasted iron mud for effective removal of heavy metals from smelting wastewater - Suiyi Zhu; Ge Dong; Yang Yu; Jiakuan Yang; Wu Yang; Wei Fan; Dandan Zhou; Jiancong Liu; Leilei Zhang; Mingxin Huo; Yi Wang (Environmental Science and Pollution Research, 2018)

Large-eddy simulation of the influence of a wavy lower boundary on the turbulence kinetic energy budget redistribution - Zongze Lu; Wei Fan; Shuang Li; Jianzhong Ge (Journal of Oceanology and Limnology, 2018)

High-density genetic map construction and QTL mapping for fiber strength on Chr24 across multiple environments in a CCRI70 recombinant inbred lines population - Xianyan Zou; Juwu Gong; Li Duan; Xiao Jiang; Zhang Zhen; Senmiao Fan; Qun Ge; Aiying Liu; Wankui Gong; Junwen Li; Yuzhen Shi; Yanling Wang; et al. (Euphytica, 2018)

Adaptation of Defensive Strategies by the Pea Aphid Mediates Predation Risk from the Predatory Lady Beetle - Li-Peng Fan; Fang Ouyang; Jian-Wei Su; Feng Ge (Journal of Chemical Ecology, 2018)

Study of aircraft icing warning algorithm based on millimeter wave radar - Jinhu Wang; Junxiang Ge; Qilin Zhang; Pan Fan; Ming Wei; Xiangchao Li (Journal of Meteorological Research, 2017)

Influence of Micropatterned Silk Fibroin Films on Human Umbilical Endothelial Cell Behaviors - Danyan Wang; Yan Sun; Xili Ding; Ge Peng; Tongqiang Zou; Haifeng Liu; Yubo Fan (Journal of Medical and Biological Engineering, 2017)

Erratum to: Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Pulling vs. pushing: effect of climate factors on periodical fluctuation of Russian and South Korean tourist demand in Hainan Island, China - Fan Chen; Jun Liu; Quansheng Ge (Chinese Geographical Science, 2017)

Biomaterial Scaffolds for Reproductive Tissue Engineering - Ge Peng; Haifeng Liu; Yubo Fan (Annals of Biomedical Engineering, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Use of mixed solid waste as a soil amendment for saline-sodic soil remediation and oat seedling growth improvement - Yuan Fan; Tian Ge; Yanli Zheng; Hua Li; Fangqin Cheng (Environmental Science and Pollution Research, 2016)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Distinct expression patterns of the GDP dissociation inhibitor protein gene (OsRhoGDI2) from Oryza sativa during development and abiotic stresses - Jun-jun Huang; Jing Zhang; Yu-fan Hao; Xin-tian Yan; Jia Shi; Gao-hua Wang; Jing-yao Du; Hui-wen Ge; Hua-hua Wang; Wei-hong Liang (Biologia, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Intein-mediated Cre protein assembly for transgene excision in hybrid progeny of transgenic Arabidopsis - Jia Ge; Lijun Wang; Chen Yang; Lingyu Ran; Mengling Wen; Xianan Fu; Di Fan; Keming Luo (Plant Cell Reports, 2016)

Socioeconomic constraints on the technological choices in rural sewage treatment - Baojing Gu; Liangcong Fan; Zechun Ying; Qingshan Xu; Weidong Luo; Ying Ge; Steffanie Scott; Jie Chang (Environmental Science and Pollution Research, 2016)

Evolution of the East China Sea sedimentary environment in the past 14 kyr: Insights from tetraethers-based proxies - HuangMin Ge; ChuanLun Zhang; Gerard J. M. Versteegh; LingLing Chen; DaiDu Fan; Liang Dong; JingJing Liu (Science China Earth Sciences, 2016)

Influences of introducing frogs in the paddy fields on soil properties and rice growth - Qing Teng; Xue-Feng Hu; Fan Luo; Chang Cheng; Xinyi Ge; Minyong Yang; Liming Liu (Journal of Soils and Sediments, 2016)

Impact of diethylhexyl phthalate on gene expression and development of mammary glands of pregnant mouse - Lan Li; Jing-Cai Liu; Yong Zhao; Fang-Nong Lai; Fan Yang; Wei Ge; Cheng-Li Dou; Wei Shen; Xi-Feng Zhang; Hong Chen (Histochemistry and Cell Biology, 2015)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Effect of Personalized Nutrition Guidance on the Birth Rate of Fetal Macrosomia in Chinese Population: A Meta-analysis of Nine Randomized Controlled Trials - Jingling Ge; Dajia Wang; Ling Fan (Cell Biochemistry and Biophysics, 2015)

Effect of Cadmium Exposure on the Histopathology of Cerebral Cortex in Juvenile Mice - XF Yang; GY Fan; DY Liu; HT Zhang; ZY Xu; YM Ge; ZL Wang (Biological Trace Element Research, 2015)

Transgenic expression of human cytoxic T-lymphocyte associated antigen4-Immunoglobulin (hCTLA4Ig) by porcine skin for xenogeneic skin grafting - Yong Wang; Hua-Qiang Yang; Wen Jiang; Na-Na Fan; Ben-Tian Zhao; Zhen Ou-Yang; Zhao-Ming Liu; Yu Zhao; Dong-Shan Yang; Xiao-Yang Zhou; Hai-Tao Shang; Lu-Lu Wang; et al. (Transgenic Research, 2015)

Association between the MMP-9−1562 C>T polymorphism and the risk of stroke: a meta-analysis - Zhen-Zhen Fan; Zhao-Ming Ge; Hong-Bin Cai; Zhi-Yan Liu; Pei Liu; Hao-Yue Wang (Molecular Biology Reports, 2014)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

Prevalence and predictive factors for poor sleep quality among migraineurs in a tertiary hospital headache clinic - Zhou Zhu; Xiaoping Fan; Xuelian Li; Ge Tan; Lixue Chen; Jiying Zhou (Acta Neurologica Belgica, 2013)

Dynamic mobilization of PGC-1α mediates mitochondrial biogenesis for the protection of RGC-5 cells by resveratrol during serum deprivation - Shida Chen; Qian Fan; Ang Li; Dongjiang Liao; Jian Ge; Alan M. Laties; Xiulan Zhang (Apoptosis, 2013)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)

Accumulation flux of nitrogen in mudflats and its implications for benthic shellfish culture - Changzi Ge; Fan Zhang; Binduo Xu; Yiping Ren; Zhenlin Liang (Aquaculture International, 2013)

Starch grain analysis reveals Late Neolithic plant utilization in the middle reaches of the Ganjiang River - ZhiWei Wan; XiaoYan Yang; QuanSheng Ge; ChangSheng Fan; GuangMing Zhou; MeiXin Jiang (Science China Earth Sciences, 2012)

Association of IL23R polymorphisms with psoriasis and psoriatic arthritis: a meta-analysis - Kun-Ju Zhu; Cheng-Yao Zhu; Ge Shi; Yi-Ming Fan (Inflammation Research, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Two new compounds from the roots of Ilex pubescens - Ting Wu; Qing-Wen Zhang; Xiao-Qi Zhang; Ge Liu; Lei Wang; Miao-Miao Jiang; Yi-Fan Feng; Wen-Cai Ye (Natural Product Research, 2012)

Satellite-based carbon stock estimation for bamboo forest with a non-linear partial least square regression technique - Huaqiang Du; Guomo Zhou; Hongli Ge; Wenyi Fan; Xiaojun Xu; Weiliang Fan; Yongjun Shi (International Journal of Remote Sensing, 2012)

Common BRCA1 and BRCA2 mutations in breast cancer families: a meta-analysis from systematic review - Furu Wang; Qiaoqiao Fang; Zhen Ge; Ningle Yu; Sanxiao Xu; Xiangyong Fan (Molecular Biology Reports, 2012)

SP1 suppresses phorbol 12-myristate 13-acetate induced up-regulation of human regucalcin expression in liver cancer cells - Hong Xu; Peihua Ni; Changqiang Chen; Yuting Yao; Xiaoping Zhao; Guanxiang Qian; Xianqun Fan; Shengfang Ge (Molecular and Cellular Biochemistry, 2011)

Estimation of aboveground carbon stock of Moso bamboo ( Phyllostachys heterocycla var. pubescens) forest with a Landsat Thematic Mapper image - Xiaojun Xu; Huaqiang Du; Guomo Zhou; Hongli Ge; Yongjun Shi; Yufeng Zhou; Weiliang Fan; Wenyi Fan (International Journal of Remote Sensing, 2011)

Cloning, molecular characterization and expression analysis of a SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE gene (CitSERK1-like) in Valencia sweet orange - Xiao-Xia Ge; Gai-En Fan; Li-Jun Chai; Wen-Wu Guo (Acta Physiologiae Plantarum, 2010)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

In vitro synergistic activity between 8-methoxypsoralen and ethambutol, isoniazid, and rifampin when used in combination against Mycobacterium tuberculosis - Fa Ge; Fanli Zeng; Na Guo; Junwen Fan; Yu Song; Siguo Liu; Xiuping Wu; Xuelin Wang; Xuming Deng; Qi Jin; Lu Yu (World Journal of Microbiology and Biotechnology, 2010)

Spatial heterogeneity and carbon contribution of aboveground biomass of moso bamboo by using geostatistical theory - Huaqiang Du; Guomo Zhou; Wenyi Fan; Hongli Ge; Xiaojun Xu; Yongjun Shi; Weiliang Fan (Plant Ecology, 2010)

Soil biological activity and their seasonal variations in response to long-term application of organic and inorganic fertilizers - Gaofei Ge; Zhaojun Li; Fenliang Fan; Guixin Chu; Zhenan Hou; Yongchao Liang (Plant and Soil, 2010)

Inheritance of sugars and acids in berries of grape (Vitis vinifera L.) - Huai-Feng Liu; Ben-Hong Wu; Pei-Ge Fan; Hai-Ying Xu; Shao-Hua Li (Euphytica, 2007)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)